All-solid secondary battery

By using fiber carbon-based materials and adhesives in the negative electrode active layer, the problem of large volume changes in lithium batteries during charging and discharging is solved, and its circulation performance and safety are improved.

JP2025066658APending Publication Date: 2025-04-23SAMSUNG SDI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024167404
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-11
Filing Date
2024-09-26
Publication Date
2025-04-23

AI Technical Summary

Technical Problem

In the prior art, lithium batteries are prone to fire or explosion when short-circuited, and their cycling performance is insufficient, which affects safety and service life.

Method used

The fiber carbon-based material and adhesive are introduced into the negative electrode active layer to ensure that the initial charging capacity of the negative electrode active layer is smaller than that of the positive electrode active layer, thereby suppressing volume changes during the charge and discharge process.

Benefits of technology

By introducing fiber carbon-based materials and adhesives, the volume changes of lithium batteries during charging and discharging are significantly reduced, and their circulation performance and safety are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066658000001_ABST
    Figure 2025066658000001_ABST
Patent Text Reader

Abstract

To provide an all-solid secondary battery having enhanced cycling characteristics.SOLUTION: An all-solid secondary battery 1 includes a cathode layer 10, an anode layer 20, and a solid electrolyte layer 30. The cathode layer 10 includes a cathode current collector 11 and a cathode active material layer 12 on one surface of the cathode current collector 11. The anode layer 20 includes an anode current collector 21 and a first anode active material layer 22 on one surface of the anode current collector 21. The first anode active material layer 22 includes an anode active material that can form an alloy or a compound with lithium, a fibrous carbon material, and a binder. A ratio (B / A) of an initial charge capacity (B) of the first anode active material layer 22 to an initial charge capacity (A) of the cathode active material layer 12 is 0.01 to 0.75. The initial charge capacity of the cathode active material layer 12 is determined by charging from a first open circuit voltage to a maximum charge voltage with respect to Li / Li+. The initial charge capacity of the first anode active material layer 22 is determined by chartering from a second open circuit voltage to 0.01 V with respect to Li / Li+.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2023-0135167, filed with the Korean Intellectual Property Office on October 11, 2023, the entire contents of which are incorporated herein by reference.

[0002] 1.Technical Field The embodiments described in this disclosure relate to all-solid-state secondary batteries. [Background technology]

[0003] 2. Description of Related Technology Recently, industrial demands and / or requests have vigorously developed batteries with high energy density and safety. For example, lithium batteries are used in a variety of applications, such as information devices, communication devices, and automobiles (e.g., electric vehicles, automobiles, and / or vehicles). Since automobiles are related to the lives of users or people, the safety of lithium batteries is important or essential.

[0004] Lithium batteries that use liquid electrolytes may have an increased risk of fire and / or explosion in the event of a short circuit. Instead of liquid electrolytes, all-solid-state secondary batteries that use solid electrolytes have been presented or proposed. Solid electrolytes are less likely to ignite than liquid electrolytes.

[0005] All-solid-state secondary batteries can or will provide improved safety by employing solid electrolytes instead of liquid electrolytes, which may reduce the possibility of fire or explosion. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Korean Patent Publication No. 10-2016-0064942 Summary of the Invention [Problem to be solved by the invention]

[0007] According to one or more embodiments, the problem to be solved by the present invention is to provide an all-solid-state secondary battery having improved cycle characteristics while suppressing or reducing volumetric change during charging and discharging by including a fibrous carbon-based material and a binder in a negative electrode active material layer having an initial charge capacity smaller than the initial charge capacity of a positive electrode active material layer.

[0008] Additional aspects will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of presented embodiments of the present disclosure. [Means for solving the problem]

[0009] According to one embodiment, a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer; the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer on one side (e.g., one or both (e.g., opposite) sides) of the positive electrode current collector; the negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer on one side (e.g., one or both (e.g., opposite) sides) of the negative electrode current collector; the first negative electrode active material layer includes a negative electrode active material that forms an alloy or a compound with lithium, a fibrous carbon-based material, and a binder; a ratio (B / A) of an initial charge capacity (B) of the first negative electrode active material layer to an initial charge capacity (A) of the positive electrode active material layer is 0.01 to 0.75; The initial charge capacity of the positive electrode active material layer is determined by the first open circuit voltage to Li / Li + is determined by charging the battery to a maximum charging voltage The initial charge capacity of the first negative electrode active material layer is calculated by dividing the first negative electrode active material layer by the second open circuit voltage by Li / Li +An all-solid-state secondary battery is provided, in which the charge voltage is determined by charging the battery to about 0.01 V vs.

[0010] According to another embodiment, a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer; the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer on one side (e.g., one or both (e.g., opposite) sides) of the positive electrode current collector; the negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer on one side (e.g., one or both (e.g., opposite) sides) of the negative electrode current collector; The first negative electrode active material layer includes a negative electrode active material that forms an alloy or compound with lithium, a fibrous carbon-based material, and a binder. Effect of the Invention

[0011] According to one aspect, by including a fibrous carbon-based material and a binder in a negative electrode active material layer having an initial charge capacity smaller than the initial charge capacity of a positive electrode active material layer, an all-solid-state secondary battery having reduced volume change during charge and discharge and improved cycle characteristics can be provided. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment. [Diagram 2] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment. [Diagram 3] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment. [Figure 4] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment. [Diagram 5] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment. [Figure 6] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment. [Figure 7] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment. [Figure 8]FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment. [Figure 9] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment. [Figure 10] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment. [Figure 11] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment. [Figure 12] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Reference will now be made in more detail to the embodiments illustrated in the accompanying drawings, where like reference numerals refer to like elements throughout and duplicate descriptions may not be provided. In this regard, the present embodiments may have different forms and should not be construed as limited to the description set forth herein. Accordingly, the present embodiments are merely described herein with reference to the drawings to illustrate aspects of the present invention. As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items. As used herein, phrases such as "at least one of," "one of," and "selected from," when preceding a list of elements, modify the entire list of elements and not the individual elements of the list. For example, "at least one of a, b, or c," "at least one selected from a, b, and c," etc., can refer to a only, b only, c only, both a and b (e.g., simultaneously), both a and c (e.g., simultaneously), both b and c (e.g., simultaneously), all of a, b, and c, or variations thereof.

[0014] Unless otherwise defined, all terms (including technical and scientific terms) used in this disclosure have the same meaning as commonly understood by a person of ordinary skill in the art to which this disclosure belongs. Furthermore, terms as defined in commonly used dictionaries should be interpreted to have a meaning consistent with their meaning in the context of the relevant art and this disclosure, and should not be interpreted as idealized or overly formal.

[0015] Exemplary embodiments are described in this disclosure based on cross-sectional views that are schematic illustrations of idealized embodiments. As such, variations from the shapes of the illustrations are to be expected as a result of, for example, manufacturing techniques and / or tolerances. Thus, the embodiments described in this disclosure should not be construed as limited to the particular shapes of the regions as illustrated in this disclosure, but should include, for example, deviations in shapes that result from manufacturing. For example, a region illustrated or described as being flat typically has rough and / or non-linear characteristics. Additionally, corners illustrated as sharp may also be rounded. Thus, the illustrated regions are schematic in nature, and the shapes are not intended to illustrate the precise shapes of the regions, and are not intended to limit the scope of the claims.

[0016] The present disclosure may be embodied in various other forms and should not be construed as being limited to the embodiments described in the present disclosure. The embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the present disclosure to those skilled in the art. The same reference numerals refer to the same components.

[0017] If an element is referred to (e.g., when referred to) as being "on" another element, it will be understood that it may be directly on the other element, or that there may be other elements intervening. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements between them.

[0018] Terms such as "first," "second," and "third" may be used in the present disclosure to describe various components, components, regions, layers, and / or sections, but these components, components, regions, layers, and / or sections should not be limited by these terms. These terms are used only to distinguish one component, component, region, layer, or section from another component, component, region, layer, or section. Thus, a first component, component, region, layer, or section described below may be referred to as a second component, component, region, layer, or section without departing from the teachings of the present disclosure.

[0019] The terms used in this disclosure are for the purpose of describing particular embodiments only and are not intended to limit the disclosure. As used herein, the singular form includes the plural form, including "at least one," unless the content clearly dictates otherwise. "At least one" should not be construed as limiting to the singular. As used in this disclosure, the term "and / or" includes any and all combinations of one or more of the list. The terms "comprises" and / or "comprising" used in the detailed description specify the presence of the stated features, regions, integers, steps, operations, components, ingredients, and / or components, and do not exclude the presence or addition of one or more other features, regions, integers, steps, operations, components, ingredients, and / or groups thereof.

[0020] Spatially relative terms such as "lower," "lower," "bottom," "top," "upper," and "top" may be used herein to easily describe the relationship of one component or feature to another component or feature. It is understood that the spatially relative terms are intended to include different orientations of the device when used or operated in addition to the orientation depicted in the figures. For example, if the device in the figures were turned upside down, a component described as "below" or "below" the other component or feature would be oriented "above" the other component or feature. Thus, the exemplary term "bottom" can encompass both an up and down orientation. The device may be otherwise oriented (rotated 90 degrees or rotated in other directions) and the spatially relative terms used in this disclosure may be interpreted accordingly.

[0021] "Group" means a group of the Periodic Table of the Elements according to the International Union of Pure and Applied Chemistry ("IUPAC") Group 1-18 classification system.

[0022] In the present disclosure, "particle size" refers to the average diameter when the particle is spherical, and refers to the average major axis length when the particle is non-spherical. Particle size can be measured using a particle size analyzer (PSA). "Particle size" is, for example, the average particle size. "Average particle size" is, for example, D50, which is the median particle size.

[0023] D50 is a particle size corresponding to 50% cumulative volume calculated from the particle side having a small particle size in the particle size distribution measured by a laser diffraction method.

[0024] D90 is the particle size corresponding to 90% cumulative volume calculated from the particle side having a small particle size in the particle size distribution measured by a laser diffraction method.

[0025] D10 is a particle size corresponding to 10% cumulative volume calculated from the particle side having a small particle size in the particle size distribution measured by a laser diffraction method.

[0026] In this disclosure, "metal" includes both metals and metalloids such as silicon and germanium, in the elemental or ionic state.

[0027] In this disclosure, "alloy" means a mixture of two or more metals.

[0028] In this disclosure, "electrode active material" means an electrode material that can undergo lithiation and delithiation.

[0029] In this disclosure, "positive electrode active material" refers to a positive electrode material that can undergo lithiation and delithiation.

[0030] In this disclosure, "negative electrode active material" refers to a negative electrode material that can undergo lithiation and delithiation.

[0031] In this disclosure, "lithiation" and "lithiating" refer to the process of adding lithium to an active positive electrode material.

[0032] In this disclosure, "delithiation" and "delithiating" refer to the process of removing lithium from an active positive electrode material.

[0033] In this disclosure, "charge" and "charging" refer to the process of providing electrochemical energy to a battery.

[0034] In this disclosure, "discharge" and "discharging" refer to the process of removing electrochemical energy from a battery.

[0035] In this disclosure, "positive electrode" and "cathode" refer to the electrodes where electrochemical reduction and lithiation occurs during the discharge process.

[0036] In this disclosure, "negative electrode" and "anode" refer to the electrodes where electrochemical oxidation and delithiation occurs during the discharge process.

[0037] As used herein, the term "substantially" and similar terms are used as terms of approximation and not of degree, and are intended to take into account inherent variations in measurements or calculations that would be recognized by one of ordinary skill in the art. Additionally, the term "about" and similar terms, when used herein in connection with a numerical value or numerical range, includes the stated value and values ​​within an acceptable range of deviation from the particular value as determined by one of ordinary skill in the art, taking into account the measurement in question and the error associated with the measurement of the particular quantity (e.g., the limitations of the measurement system). For example, "about" may refer to within one or more standard deviations, or within ±30%, 20%, 10%, 5% of the stated value.

[0038] Also, any numerical ranges mentioned herein are intended to include all subranges of the same numerical precision encompassed within the range mentioned. For example, the range "1.0-10.0" is intended to include all subranges between an implied minimum of 1.0 and an implied maximum of 10.0, i.e., having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as 2.4-7.6. Any maximum numerical limitation set forth herein is intended to include all lower numerical limitations encompassed therein, and any minimum numerical limitation set forth herein is intended to include all higher numerical limitations encompassed therein. Thus, applicants reserve the right to amend this specification, including the claims, to explicitly recite any subrange encompassed within the ranges explicitly recited herein.

[0039] While particular embodiments have been described, presently unanticipated or unforeseen alternatives, modifications, variations, improvements, and substantial equivalents may occur to applicant or those skilled in the art, and it is accordingly intended that the claims as filed, as they may be amended, include all such alternatives, modifications, variations, improvements, and substantial equivalents.

[0040] The all-solid-state secondary battery according to the illustrative embodiment will be described in further detail below.

[0041] [All-solid-state secondary battery] According to an embodiment, there is provided an all-solid-state secondary battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, the positive electrode layer comprising a positive electrode current collector and a positive electrode active material layer on one or both surfaces of the positive electrode current collector, the negative electrode layer comprising a negative electrode current collector and a first negative electrode active material layer on one surface of the negative electrode current collector, the first negative electrode active material layer comprising a negative electrode active material that forms an alloy or compound with lithium, a fibrous carbon-based material, and a binder, a ratio (B / A) of an initial charge capacity (B) of the first negative electrode active material layer to an initial charge capacity (A) of the positive electrode active material layer is 0.01 to 0.75, and the initial charge capacity of the positive electrode active material layer is Li / Li from a first open circuit voltage. +The initial charge capacity of the first negative electrode active material layer is determined by charging the first negative electrode active material layer to a maximum charging voltage relative to a second open circuit voltage Li / Li + The measured voltage is determined by charging the battery to approximately 0.01 V.

[0042] The fibrous carbonaceous material can provide a conductive path between the plurality of negative electrode active materials. Therefore, an increase in the internal resistance of the first negative electrode active material layer can be easily suppressed or reduced. Therefore, an increase in the internal resistance of the all-solid-state secondary battery can be suppressed or reduced.

[0043] The fibrous carbonaceous material acts as a support / buffer between the multiple negative electrode active materials, which more easily reduces the volume change of the first negative electrode active material layer caused by the deposition and / or dissolution of lithium during charging and discharging, thereby reducing the volume change during charging and discharging of the all-solid-state secondary battery.

[0044] The binder binds the negative electrode active material and the fibrous carbon-based material, which can more effectively prevent the conductive path between the negative electrode active material and the fibrous carbon-based material from being broken down due to the volume change of the negative electrode active material during the process of lithium precipitation and / or dissolution during charging and discharging, thereby preventing non-uniformity in the electrode reaction of the all-solid-state secondary battery.

[0045] The binder may improve the adhesive strength between the first negative electrode active material layer and the solid electrolyte layer, or between the first negative electrode active material layer and the current collector. For example, the binder may improve the wettability between the first negative electrode active material layer and the solid electrolyte layer, or between the first negative electrode active material layer and the current collector. Therefore, the binder may more effectively reduce an increase in interface resistance due to the formation of voids between the first negative electrode active material layer and the solid electrolyte layer, or between the first negative electrode active material layer and the current collector. The cycle characteristics of the all-solid-state secondary battery may be improved.

[0046] If the first negative electrode active material layer does not contain a binder (for example, when it does not contain a binder), the first negative electrode active material layer may be detached from the solid electrolyte layer and / or the negative electrode current collector, thereby exposing the surface of the solid electrolyte layer and / or the negative electrode current collector. For example, the exposed negative electrode current collector may cause a short circuit. The cycle characteristics of the all-solid-state secondary battery may be degraded.

[0047] 1 to 12, the all-solid-state secondary battery 1 includes a positive electrode layer 10, a negative electrode layer 20, and a solid electrolyte layer 30 between the positive electrode layer 10 and the negative electrode layer 20. The positive electrode layer 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12 on one surface of the positive electrode current collector 11. The negative electrode layer 20 includes a negative electrode current collector 21 and a first negative electrode active material layer 22 on one surface of the negative electrode current collector 21. The first negative electrode active material layer 22 includes a negative electrode active material capable of forming an alloy with lithium or forming a compound with lithium, a fibrous carbon-based material, and a binder. The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer is 0.01 to 0.75. The initial charge capacity of the positive electrode active material layer is calculated based on a first open circuit voltage (1st open circuit voltage) as Li / Li + The initial charge capacity of the first negative electrode active material layer is determined by charging the first negative electrode active material layer to a maximum charging voltage relative to the second open circuit voltage. + The measured voltage is determined by charging the battery to approximately 0.01 V.

[0048] [Negative electrode layer] [Negative electrode layer: negative electrode active material] 1 to 12, the negative electrode layer 20 includes a first negative electrode active material layer 22. The first negative electrode active material layer 22 includes a negative electrode active material that forms an alloy or compound with lithium.

[0049] The negative electrode active material is, for example, a negative electrode material that forms an alloy with lithium or a negative electrode material that forms a compound with lithium.

[0050] The first negative electrode active material layer 22 includes a negative electrode active material, and the negative electrode active material has, for example, a particulate form. The size of the negative electrode active material having a particulate form is, for example, 2 μm or less, 1 μm or less, 500 nm or less, 300 nm or less, or 100 nm or less. The size of the negative electrode active material having a particulate form is, for example, 10 nm to 2 μm, 100 nm to 2 μm, 200 nm to 2 μm, 500 nm to 2 μm, or 500 nm to 1.5 μm. In other embodiments, the size of the negative electrode active material having a particulate form is, for example, 10 nm to 2 μm, 10 nm to 1 μm, 10 nm to 500 nm, 10 nm to 300 nm, 10 nm to 200 nm, or 10 nm to 100 nm. When the negative electrode active material has a size in such a range, the negative electrode active material can more easily perform reversible absorbing and / or desorbing of lithium during charging and discharging. The size of the negative electrode active material is, for example, the average particle size of the negative electrode active material. The average particle size of the negative electrode active material is, for example, the median diameter (D50) measured using a laser type particle size distribution meter.

[0051] The aspect ratio of the negative electrode active material is, for example, 5 or less, 4 or less, 3 or less, or 2 or less. The aspect ratio of the negative electrode active material is, for example, 1 to 5, 1 to 4, 1 to 3, or 1 to 2. When the negative electrode active material has an aspect ratio in such a range, the negative electrode active material can be more uniformly distributed in the first negative electrode active material layer 22. As a result, non-uniformity in the volume change of the negative electrode active material during charging and discharging can be suppressed. The aspect ratio of the negative electrode active material can be measured, for example, by a scanning electron microscope.

[0052] The negative electrode active material contained in the first negative electrode active material layer 22 includes, for example, a metal-based negative electrode active material.

[0053] The metal-based negative electrode active material may be, but is not limited to, silicon (Si), gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), or a combination thereof, and any metal-based negative electrode active material that can form an alloy or compound with lithium in the art may be used. For example, nickel (Ni) is not a metal-based negative electrode active material because it does not form an alloy with lithium.

[0054] The first negative electrode active material layer 22 does not contain, for example, a carbon-based negative electrode active material. When the first negative electrode active material layer 22 does not contain a carbon-based negative electrode active material, the energy density of the first negative electrode active material layer 22 can be further improved.

[0055] In another embodiment, the first negative electrode active material layer 22 includes a negative electrode active material, and the negative electrode active material may be, for example, a composite negative electrode active material. The composite negative electrode active material may include, for example, a carbon-based support and a metal-based negative electrode active material supported on the carbon-based support. When the composite negative electrode active material has such a structure, uneven distribution of the metal-based negative electrode active material in the first negative electrode active material layer 22 is prevented or reduced, and a substantially uniform distribution is obtained. As a result, the cycle characteristics of the all-solid-state secondary battery 1 including the first negative electrode active material layer 22 may be further improved. The metal-based negative electrode active material supported on the carbon-based support includes, for example, silicon (Si), gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), tellurium (Te), and zinc (Zn). The carbon-based support is, for example, amorphous carbon. Examples of amorphous carbon include carbon black (CB), acetylene black (AB), furnace black (FB), ketjen black (KB), graphene, and activated carbon, but are not limited thereto. Any material classified as amorphous carbon in the art can be used. Amorphous carbon is carbon that has no crystallinity or has very low crystallinity, and is classified as crystalline carbon or graphite-based carbon. The composite negative electrode active material has, for example, a particle shape. The particle size of the composite negative electrode active material having a particle shape is, for example, 10 nm to 2 μm, 10 nm to 1 μm, 10 nm to 500 nm, 10 nm to 200 nm, or 10 nm to 100 nm. When the composite negative electrode active material has a particle size in such a range, reversible absorbing and / or desorbing of lithium during charging and discharging may be easier. The metal-based negative electrode active material supported on the support may have, for example, a particulate form. The particle size of the metal-based negative electrode active material may be, for example, 1 nm to 200 nm, 1 nm to 150 nm, 5 nm to 100 nm, or 10 nm to 50 nm. The carbon-based support has, for example, a particulate form.The particle size of the carbon-based support may be, for example, 10 nm to 2 μm, 10 nm to 1 μm, 10 nm to 500 nm, 10 nm to 200 nm, or 10 nm to 100 nm. By having the carbon-based support have a particle size in such a range, it can be more uniformly arranged in the first negative electrode active material layer. The carbon-based support may be, for example, nanoparticles having a particle size of 500 nm or less. The particle size of the composite negative electrode active material, the particle size of the metal-based negative electrode active material, and the particle size of the carbon-based support are, for example, average particle sizes. The average particle size is, for example, a median diameter (D50) measured using a laser type particle size distribution meter. In other embodiments, the average particle size is, for example, automatically determined using software from an electron microscope image, or is determined manually.

[0056] [Anode layer: fibrous carbon material] The first negative electrode active material layer 22 contains a fibrous carbonaceous material in addition to the negative electrode active material.

[0057] The first negative electrode active material layer 22 includes a mixture of a negative electrode active material that forms an alloy or compound with lithium and a fibrous carbon-based material. For example, the first negative electrode active material layer 22 includes a mixture of a fibrous carbon-based material and one or more selected from the group consisting of silicon (Si), gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). The mixture ratio of the fibrous carbon-based material and the mixture of silicon and the like is, for example, 99:1 to 1:99, 10:1 to 1:10, 1:1 to 1:9, 1:1 to 1:8, 1:1 to 1:7, 1:1 to 1:6, 1:1 to 1:5, 1:1 to 1:4, or 1:1 to 1:3 by weight, but is not necessarily limited to such a range and is selected according to the required characteristics of the all-solid-state secondary battery 1. When the fibrous carbon material and the negative electrode active material have such compositions, the cycle characteristics of the all-solid-state secondary battery 1 are further improved.

[0058] The first negative electrode active material layer 22 includes a mixture of first particles made of a metal and second particles made of a fibrous carbon-based material. The metal includes, for example, silicon (Si), gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), or a combination thereof. The content of the second particles is 1 to 99 wt%, 1 to 70 wt%, more than 10 to 70 wt%, 11 to 60 wt%, or 12 to 50 wt%, based on the total weight of the mixture. When the fibrous carbon-based material has a content in such a range, for example, the cycle characteristics of the all-solid-state secondary battery 1 are further improved.

[0059] The size of the negative electrode active material that forms an alloy or compound with lithium is, for example, smaller than the length of the fibrous carbon-based material. The length of the fibrous carbon-based material is larger than the size of the negative electrode active material, so that the fibrous carbon-based material can act as a support and / or a buffer between a plurality of negative electrode active materials. The fibrous carbon-based material is disposed between a plurality of negative electrode active materials, so that the stress caused by the volume change of the negative electrode active material due to the deposition and / or dissolution of lithium during charging and discharging can be effectively alleviated. As a result, the volume change of the first negative electrode active material layer 22 during charging and discharging can be more effectively suppressed. The ratio of the size of the negative electrode active material to the length of the fibrous carbon-based material may be, for example, 1:10 to 1:2000, 1:10 to 1:1000, 1:10 to 1:500, 1:10 to 1:200, 1:10 to 1:100, 1:10 to 1:50, or 1:10 to 1:20. When the ratio of the size of the negative electrode active material to the length of the fibrous carbon material falls within such a range, for example, the cycle characteristics of the all-solid-state secondary battery 1 are further improved.

[0060] The fibrous carbon-based material may be, for example, a conductive carbon-based material. The fibrous carbon-based material has conductivity, and thus can provide a conductive path inside the first negative electrode active material layer 22. The fibrous carbon-based material can further effectively reduce the internal resistance of the first negative electrode active material layer 22. As a result, the cycle characteristics of the all-solid-state secondary battery 1 are improved. The first negative electrode active material layer 22 does not additionally contain other carbon-based conductive materials other than the fibrous carbon-based material. The first negative electrode active material layer 22 does not contain other carbon-based conductive materials other than the fibrous carbon-based material, and thus the energy density of the first negative electrode active material layer 22 can be further improved.

[0061] The aspect ratio of the fibrous carbon-based material may be, for example, 10 or more, 20 or more, 30 or more, or 50 or more. The aspect ratio of the fibrous carbon-based material may be, for example, 2000 or less, 1000 or less, 500 or less, 200 or less, or 100 or less. The aspect ratio of the fibrous carbon-based material may be, for example, 10 to 2000, 20 to 2000, 30 to 2000, or 50 to 2000. The aspect ratio of the fibrous carbon-based material may be, for example, 10 to 2000, 10 to 1000, 10 to 500, 10 to 200, 10 to 100, 10 to 50, or 10 to 20. The aspect ratio of the fibrous carbon-based material is, for example, the ratio of the major axis length of the fibrous carbon-based material, i.e., the length of the fibrous carbon-based material to the shortened length perpendicular to the major axis, i.e., the diameter of the second carbon-based material. In this specification, the "aspect ratio" refers to an average aspect ratio and may be determined from a scanning electron microscope (SEM) image. When the fibrous carbon-based material has an aspect ratio in such a range, the fibrous carbon-based material further lengthens the conducting path inside the first negative electrode active material layer 22. The fibrous carbon-based material forms a three-dimensional conductive network within the first negative electrode active material layer 22, which may more effectively reduce the internal resistance of the first negative electrode active material layer 22. As a result, the internal resistance of the all-solid-state secondary battery 1 is reduced. For example, the high-rate characteristics of the all-solid-state secondary battery 1 may be improved.

[0062] The fibrous carbon-based material may include, for example, an amorphous fibrous carbon-based material, a crystalline fibrous carbon-based material, or a combination thereof. When the fibrous carbon-based material includes an amorphous fibrous carbon-based material, the negative reaction between lithium and the fibrous carbon-based material may be more effectively suppressed. When the all-solid-state secondary battery 1 is charged and discharged, the reversibility of the electrode reaction is improved, and thus the cycle characteristics of the all-solid-state secondary battery 1 may be improved.

[0063] The diameter of the fibrous carbon-based material may be, for example, 50 nm or less, 30 nm or less, 20 nm or less, or 10 nm or less. The diameter of the fibrous carbon-based material may be, for example, 1 nm to 50 nm, 1 nm to 30 nm, or 1 nm to 10 nm. When the fibrous carbon-based material has a diameter in such a range, the internal resistance of the first negative electrode active material layer 22 can be effectively reduced, and the first negative electrode active material layer 22 can be easily dispersed in a solvent and / or slurry during production of the first negative electrode active material layer 22.

[0064] The length of the fibrous carbon-based material may be, for example, 1000 μm or less, 100 μm or less, 50 μm or less, 10 μm or less, 5 μm or less, 2 μm or less, 1 μm or less, 500 nm or less, or 300 nm or less. The length of the fibrous carbon-based material may be, for example, 100 nm to 1000 μm, 100 nm to 500 μm, 100 nm to 100 μm, 100 nm to 50 μm, 100 nm to 10 μm, 100 nm to 5 μm, 100 nm to 2 μm, 100 nm to 1 μm, 100 nm to 500 nm, or 100 nm to 300 nm. The length of the fibrous carbon-based material may be, for example, 500 nm to 1000 μm, 500 nm to 500 μm, 500 nm to 100 μm, 500 nm to 50 μm, 500 nm to 10 μm, 1 μm to 10 μm, or 2 μm to 8 μm. The internal resistance of the electrode can be reduced as the length of the fibrous carbon-based material increases. In the present disclosure, when the material is spherical or circular, "diameter" refers to the circle diameter or average circle diameter, and when the material is non-spherical or non-circular, "diameter" refers to the major axis length or average major axis length.

[0065] The fibrous carbon-based material can include, for example, a fibrous carbon nanostructure. The fibrous carbon nanostructure can include, for example, a carbon nanofiber, a carbon nanotube, a carbon nanobelt, or a combination thereof.

[0066] The carbon nanotubes may include, for example, carbon nanotube primary structures, carbon nanotube secondary structures formed by agglomeration of a plurality of carbon nanotube primary particles, or a combination thereof.

[0067] The carbon nanotube primary structure is one carbon nanotube unit. The carbon nanotube unit is a graphite sheet having a cylindrical shape with a nano-sized diameter, and the 2 It has a bond structure. Depending on the angle and structure of the curve of the graphite sheet, it can exhibit conductive or semiconductive properties. Carbon nanotube units can be classified into single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), and multi-walled carbon nanotubes (MWCNT), depending on the number of bonds that make up the wall. The thinner the wall thickness of a carbon nanotube unit, the lower the resistance.

[0068] The carbon nanotube primary structure may include, for example, a single-walled carbon nanotube (SWCNT), a double-walled carbon nanotube (DWCNT), and a multi-walled carbon nanotube (MWCNT), or a combination thereof. The diameter of the carbon nanotube primary structure may be, for example, 1 nm or more, or 2 nm or more. The diameter of the carbon nanotube primary structure may be, for example, 20 nm or less, or 10 nm or less. The diameter of the carbon nanotube primary structure may be, for example, 1 nm to 20 nm, 1 nm to 15 nm, or 1 nm to 10 nm. The length of the carbon nanotube primary structure may be, for example, 100 nm or more, or 200 nm or more. The length of the carbon nanotube primary structure may be, for example, 2 μm or less, 1 μm or less, 500 nm or less, or 300 nm or less. The length of the carbon nanotube primary structure may be, for example, 100 nm to 2 μm, 100 nm to 1 μm, 100 nm to 500 nm, 100 nm to 400 nm, 100 nm to 300 nm, or 200 nm to 300 nm. The diameter and length of the carbon nanotube primary structure may be measured from a scanning electron microscope (SEM) or a transmission electron microscope (TEM) image. In another embodiment, the diameter and / or length of the carbon nanotube primary structure may be measured by a laser diffraction method.

[0069] The carbon nanotube secondary structure is a structure formed by assembling the carbon nanotube primary structures entirely or partially into a bundle or rope shape. The carbon nanotube secondary structure may include, for example, a bundle-type carbon nanotube, a rope-type carbon nanotube, or a combination thereof. The diameter of the carbon nanotube secondary structure may be, for example, 2 nm or more or 3 nm or more. The diameter of the carbon nanotube secondary structure may be, for example, 50 nm or less, 30 nm or less, 20 nm or less, or 10 nm or less. The diameter of the carbon nanotube secondary structure may be, for example, 2 nm to 50 nm, 2 nm to 30 nm, or 2 nm to 20 nm. The length of the carbon nanotube secondary structure may be, for example, 500 nm or more, 700 nm or more, 1 μm or more, or 10 μm or more. The length of the carbon nanotube secondary structure may be, for example, 1000 μm or less, 500 μm or less, or 100 μm or less. The length of the carbon nanotube secondary structure may be, for example, 500 nm to 1000 μm, 500 nm to 500 μm, 500 nm to 200 μm, 500 nm to 100 μm, 500 nm to 50 μm, 500 nm to 10 μm, 1 μm to 10 μm, or 2 μm to 8 μm. The diameter and length of the carbon nanotube secondary structure may be measured from a scanning electron microscope (SEM) image or an optical microscope image. In another embodiment, the diameter and / or length of the carbon nanotube secondary structure may be measured by a laser diffraction method.

[0070] The carbon nanotube secondary structures can be used to manufacture the first negative electrode active material layer 22 after being converted into carbon nanotube primary structures by, for example, dispersing them in a solvent or the like. [Negative electrode layer: binder]

[0071] The first negative electrode active material layer 22 contains a binder in addition to the negative electrode active material and the fibrous carbon-based material. The binder is, for example, a polymer binder. The binder contained in the first negative electrode active material layer 22 is, for example, a binder containing a polar functional group. In the binder containing a polar functional group, the polar functional group includes, for example, a carboxyl group, a hydroxyl group, an amide group, an aldehyde group, or a combination thereof. A part or all of the polar functional group can be substituted with lithium. The polar functional group can include, for example, a lithium-substituted or unsubstituted carboxyl group, a lithium-substituted or unsubstituted hydroxyl group, a lithium-substituted or unsubstituted amide group, a lithium-substituted or unsubstituted aldehyde group, or a combination thereof. The binder can include, for example, polyacrylic acid, lithium-substituted polyacrylic acid, or a combination thereof. In the lithium-substituted polyacrylic acid, the degree of substitution of lithium is, for example, 0.1 to 1.0. The degree of lithium substitution is the ratio of carboxyl groups substituted with lithium to the carboxyl groups (-COOH) and lithium-substituted carboxyl groups (-COOLi) contained in the polyacrylic acid.

[0072] The polymer may include, for example, polyacrylic acid represented by the following Chemical Formula 1: <Chemical formula 1>

[0073] [ka]

[0074] In the above formula, R1, R2, and R3 are each independently hydrogen, halogen, an alkyl group having 1 to 10 carbon atoms and substituted or unsubstituted with a halogen, an alkenyl group having 2 to 10 carbon atoms and substituted or unsubstituted with a halogen, an alkynyl group having 2 to 10 carbon atoms and substituted or unsubstituted with a halogen, a cycloalkyl group having 5 to 10 carbon atoms and substituted or unsubstituted with a halogen, an aryl group having 6 to 20 carbon atoms and substituted or unsubstituted with a halogen, or a heteroaryl group having 2 to 20 carbon atoms and substituted or unsubstituted with a halogen, M is hydrogen or lithium, and n is a degree of polymerization of 10 to 10,000. The weight average molecular weight of the polymer is, for example, 1,000 Dalton to 250,000 Dalton or 10,000 Dalton to 200,000 Dalton. The weight average molecular weight of the polymer can be measured, for example, by GPC (Gel Permeation Chromatography) against a polystyrene standard sample.

[0075] The binder includes a lithium-substituted polar functional group, so that the ion conductivity of the first negative electrode active material layer 22 including the binder can be further improved. For example, the internal resistance of the first negative electrode active material layer 22 including a binder including a lithium-substituted polar functional group is even lower than the internal resistance of the first negative electrode active material layer 22 including a binder not including a lithium-substituted polar functional group. As a result, the cycle characteristics of the all-solid-state secondary battery 1 including the first negative electrode active material layer 22 including a binder including a lithium-substituted polar functional group can be improved.

[0076] The first negative electrode active material layer 22 may additionally include another binder. The first negative electrode active material layer 22 may additionally include another binder, and the other binder may be, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but is not necessarily limited thereto, and any binder used as a binder in the art may be used.

[0077] Since the first negative electrode active material layer 22 contains a binder, the first negative electrode active material layer 22 is stabilized on the negative electrode current collector 21. In addition, cracks in the first negative electrode active material layer 22 are suppressed despite changes in volume and / or relative position of the first negative electrode active material layer 22 during charging and discharging. For example, if the first negative electrode active material layer 22 does not contain a binder, the first negative electrode active material layer 22 may be easily separated from the negative electrode current collector 21. When the first negative electrode active material layer 22 is detached from the negative electrode current collector 21, the negative electrode current collector 21 comes into contact with the solid electrolyte layer 30 at the portion where the negative electrode current collector 21 is exposed, increasing the possibility of short circuit occurrence. The first negative electrode active material layer 22 is prepared, for example, by applying a slurry in which materials constituting the first negative electrode active material layer 22 are dispersed onto the negative electrode current collector 21 and drying the slurry. The negative electrode active material and the fibrous carbon-based material can be stably dispersed in the slurry by including a binder in the first negative electrode active material layer 22. For example, when the slurry is applied onto the negative electrode current collector 21 by a screen printing method, clogging of the screen (for example, clogging due to aggregates of the negative electrode active material) can be suppressed or reduced.

[0078] The binder content may be 0.1 to 20 parts by weight, 0.1 to 15 parts by weight, 1 to 10 parts by weight, or 5 to 10 parts by weight relative to 100 parts by weight of the negative electrode active material. By having a binder content in such a range, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.

[0079] [Negative electrode layer: Other additives] The first negative electrode active material layer 22 can further contain additives used in conventional all-solid-state secondary batteries 1, such as a filler, a coating agent, a dispersant, an ion-conducting assistant, and the like.

[0080] [Negative electrode layer: first negative electrode active material layer] The initial charge capacity (B) of the first negative electrode active material layer 22 is, for example, 75% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the initial charge capacity (A) of the positive electrode active material layer 12.

[0081] The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer 22 to the initial charge capacity (A) of the positive electrode active material layer 12 is, for example, 0.01 to 0.75, 0.01 to 0.7, 0.01 to 0.6, 0.01 to 0.5, 0.01 to 0.6, 0.01 to 0.5, 0.01 to 0.4, 0.01 to 0.3, 0.01 to 0.2, or 0.01 to 0.1. The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer 22 to the initial charge capacity (A) of the positive electrode active material layer 12 is, for example, 0.05 to 0.75, 0.1 to 0.7, 0.1 to 0.6, 0.2 to 0.6, 0.2 to 0.5, or 0.2 to 0.45. The initial charge capacity of the positive electrode active material layer 12 is calculated by dividing the first open circuit voltage by Li / Li + The initial charge capacity of the first negative electrode active material layer 22 is determined by charging the first negative electrode active material layer 22 to a maximum charging voltage relative to the second open circuit voltage Li / Li + The maximum charging voltage is determined by charging to 0.01 V vs. Li / Li. The maximum charging voltage is determined by the type of positive electrode active material. The maximum charging voltage may be, for example, 1.5 V, 2.0 V, 2.5 V, 3.0 V, 3.5 V, 4.0 V, 4.2 V, or 4.3 V. For example, the maximum charging voltage of Li2S or a Li2S composite is + For example, the maximum charging voltage of a lithium transition metal oxide can be determined to be between 2.5 and 3.0 V with respect to Li / Li +The voltage can be determined to be between 3.0 and 4.5 V.

[0082] The initial charge capacity (mAh) of the positive electrode active material layer 12 is obtained by multiplying the charge specific capacity (mAh / g) of the positive electrode active material by the mass (g) of the positive electrode active material in the positive electrode active material layer 12. When a plurality of types of positive electrode active materials are used, the charge capacity density×mass value is calculated for each positive electrode active material, and the sum of these values ​​is the initial charge capacity of the positive electrode active material layer 12. The initial charge capacity of the first negative electrode active material layer 22 is also calculated in the same manner. The initial charge capacity of the first negative electrode active material layer 22 is obtained by multiplying the charge capacity density (mAh / g) of the negative electrode active material by the mass of the negative electrode active material in the first negative electrode active material layer 22. When various types of negative electrode active materials are used, the charge capacity density×mass value is calculated for each negative electrode active material, and the sum of these values ​​is the initial charge capacity of the first negative electrode active material layer 22. The charge capacity density of each of the positive electrode active material and the negative electrode active material can be measured using an all-solid-state half-cell using lithium metal as a counter electrode. The current density at which the initial charge capacity of each of the positive electrode active material layer 12 and the first negative electrode active material layer 22 is constant, for example, 0.1 mA / cm 2 For the positive electrode, the measurement can be performed by measuring the charge voltage from the first open circuit voltage (OCV) to the maximum charging voltage, e.g., 3.0 V (vs. Li / Li + For the negative electrode, the measurements can be performed at an operating voltage from the second open circuit voltage (OCV) to 0.01 V versus the negative electrode, e.g., lithium metal. For example, an all-solid-state half-cell with a positive electrode active material layer can have a current density of 0.1 mA / cm from the first open circuit voltage to 3.0 V. 2 The all-solid-state half-cell having the first negative electrode active material layer can be charged with a constant current of 0.1 mA / cm from the second open circuit voltage to 0.01 V. 2 The current density during constant current charging is, for example, 0.2 mA / cm 2 , or 0.5mA / cm 2The all-solid-state half-cell having the positive electrode active material layer can be charged, for example, from the first open circuit voltage to 2.5 V, 2.0 V, 3.5 V, 4.0 V, or 4.5 V. The maximum charging voltage of the positive electrode active material layer can be determined by the maximum voltage of the battery that satisfies the safety conditions according to JISC8712:2015 of the Japanese Standards Association.

[0083] If the initial charge capacity of the first negative electrode active material layer 22 is excessively small, the thickness of the first negative electrode active material layer 22 becomes very thin, and thus lithium dendrites formed between the first negative electrode active material layer 22 and the negative electrode current collector 21 during repeated charge and discharge processes collapse the first negative electrode active material layer 22, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. If the charge capacity of the first negative electrode active material layer 22 increases excessively, the energy density of the all-solid-state secondary battery 1 decreases and the internal resistance of the all-solid-state secondary battery 1 due to the first negative electrode active material layer 22 increases, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1.

[0084] The thickness of the first negative electrode active material layer 22 is, for example, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the thickness of the positive electrode active material layer 12. The thickness of the first negative electrode active material layer 22 is, for example, 1 to 50%, 1 to 40%, 1 to 30%, 1 to 20%, or 1 to 10% of the thickness of the positive electrode active material layer 12. The thickness of the first negative electrode active material layer 22 is, for example, 1 to 50 μm, 2 to 40 μm, 3 to 30 μm, 4 to 20 μm, or 5 μm to 20 μm. The thickness of the first negative electrode active material layer 22 is, for example, 5 to 50 μm, 10 to 50 μm, 15 to 50 μm, 20 to 50 μm, or 25 μm to 50 μm. If the thickness of the first negative electrode active material layer 22 is excessively thin, lithium dendrites formed between the first negative electrode active material layer 22 and the negative electrode current collector 21 collapse the first negative electrode active material layer 22, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. If the thickness of the first negative electrode active material layer 22 is excessively increased, the energy density of the all-solid-state secondary battery 1 decreases, and the internal resistance of the all-solid-state secondary battery 1 due to the first negative electrode active material layer 22 increases, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. If the thickness of the first negative electrode active material layer 22 is reduced, for example, the initial charge capacity of the first negative electrode active material layer 22 also decreases.

[0085] [Negative electrode: second negative electrode active material layer] Referring to FIG. 3, the all-solid-state secondary battery 1 may further include, for example, a second negative electrode active material layer 24 disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 after charging. The second negative electrode active material layer 24 is a metal layer containing lithium or a lithium alloy. The metal layer contains lithium or a lithium alloy. Therefore, since the second negative electrode active material layer 24 is a metal layer containing lithium, it acts as, for example, a lithium reservoir. The lithium alloy may be, for example, a Li-Al alloy, a Li-Sn alloy, a Li-In alloy, a Li-Ag alloy, a Li-Au alloy, a Li-Zn alloy, a Li-Ge alloy, a Li-Si alloy, etc., but is not limited thereto, and any alloy used as a lithium alloy in the art may be used. The second negative electrode active material layer 24 may be one of such alloys, or may be composed of lithium, or may be composed of various alloys. The second negative electrode active material layer 24 may be, for example, a plated layer. The second negative electrode active material layer 24 is deposited between the first negative electrode active material layer 22 and the negative electrode current collector 21 during charging of the all-solid-state secondary battery 1, for example.

[0086] The thickness of the second negative electrode active material layer 24 is not particularly limited, and may be, for example, 1 to 200 μm, 1 to 150 μm, 1 to 100 μm, 1 to 50 μm, 1 to 30 μm, 1 to 22 μm, or 1 μm to 10 μm. If the thickness of the second negative electrode active material layer 24 is too thin, it is difficult for the second negative electrode active material layer 24 to perform the role of a lithium reservoir. If the thickness of the second negative electrode active material layer 24 is too thick, the mass and volume of the all-solid-state secondary battery 1 increase, and the cycle characteristics of the all-solid-state secondary battery 1 may rather deteriorate.

[0087] The thickness of the second negative electrode active material layer 24 is, for example, even thinner than the thickness of the first negative electrode active material layer 22. The thickness of the second negative electrode active material layer 24 may be, for example, 70% or less, 60% or less, 50% or less, 40% or less, or 30% or less of the thickness of the first negative electrode active material layer 22. The thickness of the second negative electrode active material layer 24 may be, for example, 1 to 70%, 1 to 60%, 1 to 50%, 1 to 40%, or 1 to 30% of the thickness of the first negative electrode active material layer 22. By making the thickness of the second negative electrode active material layer 24 thinner than the thickness of the first negative electrode active material layer 22, the volume change during charging and discharging of the all-solid-state secondary battery can be suppressed. As a result, the deterioration due to the volume change of the all-solid-state secondary battery can be suppressed.

[0088] In another embodiment, the second negative electrode active material layer 24 in the all solid state secondary battery 1 may be disposed, for example, between the negative electrode current collector 21 and the first negative electrode active material layer 22 before the all solid state secondary battery 1 is assembled. When the second negative electrode active material layer 24 is disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 before the all solid state secondary battery 1 is assembled, the second negative electrode active material layer 24 is a metal layer containing lithium and therefore acts as a lithium reservoir. For example, a lithium foil may be disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 before the all solid state secondary battery 1 is assembled.

[0089] When the second negative electrode active material layer 24 is precipitated by charging after the all-solid-state secondary battery 1 is assembled, the energy density of the all-solid-state secondary battery 1 increases because the all-solid-state secondary battery 1 does not include the second negative electrode active material layer 24 when assembled. When the all-solid-state secondary battery 1 is charged, the first negative electrode active material layer 22 is charged beyond its charge capacity. That is, the first negative electrode active material layer 22 is overcharged. At the beginning of charging, lithium is absorbed in the first negative electrode active material layer 22. The negative electrode active material contained in the first negative electrode active material layer 22 forms an alloy or compound with the lithium ions transferred from the positive electrode 10. If the first negative electrode active material layer 22 is charged beyond its capacity, for example, lithium is precipitated on the back surface of the first negative electrode active material layer 22, that is, between the negative electrode current collector 21 and the first negative electrode active material layer 22, and the precipitated lithium forms a metal layer corresponding to the second negative electrode active material layer 24. The second negative electrode active material layer 24 is a metal layer mainly composed of lithium (i.e., metallic lithium). Such a result is obtained, for example, because the negative electrode active material contained in the first negative electrode active material layer 22 contains a material that forms an alloy or compound with lithium. During discharge, the lithium in the first negative electrode active material layer 22 and the second negative electrode active material layer 24, i.e., the metal layer, is ionized and moves toward the positive electrode 10. Therefore, lithium can be used as the negative electrode active material in the all-solid-state secondary battery 1. In addition, since the first negative electrode active material layer 22 covers the second negative electrode active material layer 24, it serves as a protective layer for the second negative electrode active material layer 24, i.e., the metal layer, and also serves to suppress the deposition growth of lithium dendrites. Therefore, the short circuit and capacity decrease of the all-solid-state secondary battery 1 are suppressed, and as a result. The cycle characteristics of the all-solid-state secondary battery 1 are improved. Furthermore, when the second negative electrode active material layer 24 is disposed by charging after the assembly of the all-solid-state secondary battery 1, the negative electrode 20, i.e., the negative electrode current collector 21 and the first negative electrode active material layer 22, and the region therebetween are Li-free regions that do not contain lithium (Li) in the initial state or after full discharge of the all-solid-state secondary battery 1.

[0090] [Negative electrode: negative electrode current collector] The negative electrode current collector 21 is made of, for example, a material that does not react with lithium, i.e., does not form any alloy or compound. The material constituting the negative electrode current collector 21 is, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), etc., but is not necessarily limited thereto, and any material used as an electrode current collector in the relevant technical field can be used. The negative electrode current collector 21 can be made of one of the above-mentioned metals, or two or more metal alloys or coating materials. The negative electrode current collector 21 is, for example, in the form of a plate or foil.

[0091] Referring to FIG. 2, the all-solid-state secondary battery 1 may further include a thin film 23 including an element capable of forming an alloy with lithium on one surface of the negative electrode current collector 21. The thin film 23 is disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22. The thin film 23 includes, for example, an element capable of forming an alloy with lithium. The element capable of forming an alloy with lithium may be, for example, gold, silver, zinc, tin, indium, silicon, aluminum, bismuth, etc., but is not limited thereto, and any element capable of forming an alloy with lithium in the art may be used. The thin film 23 may be composed of one of these metals or an alloy of various metals. By disposing the thin film 23 on one surface of the negative electrode current collector 21, for example, the deposition form of the second negative electrode active material layer 24 deposited between the thin film 23 and the first negative electrode active material layer 22 may be further flattened, and the cycle characteristics of the all-solid-state secondary battery 1 may be further improved.

[0092] The thickness of the thin film 23 is, for example, 1 nm to 800 nm, 10 nm to 700 nm, 50 nm to 600 nm, or 100 nm to 500 nm. If the thickness of the thin film 23 is less than 1 nm, the function of the thin film 23 is difficult to be exerted. If the thickness of the thin film 23 is excessively thick, the thin film 23 itself absorbs lithium, the amount of lithium precipitated at the negative electrode decreases, the energy density of the all-solid-state battery decreases, and the cycle characteristics of the all-solid-state secondary battery 1 may decrease. The thin film 23 may be disposed on the negative electrode current collector 21 by, for example, a vacuum deposition method, a sputtering method, a plating method, or the like, but is not necessarily limited to such a method, and any method that can form the thin film 23 in the art may be used.

[0093] Although not shown in the drawings, the negative electrode current collector 21 may include, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The polymer may be an insulating polymer. When the base film includes an insulating thermoplastic polymer, the base film is softened or liquefied in the event of a short circuit, thereby cutting off the operation of the battery and suppressing a sudden increase in current. The metal layer may include, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), or an alloy thereof. The negative electrode current collector 21 may additionally include a metal piece and / or a lead tab. For more details regarding the base film, metal layer, metal chip, and lead tab of the negative electrode current collector 21, please refer to the above-mentioned positive electrode current collector 11. By having such a structure of the negative electrode current collector 21, the weight of the negative electrode can be reduced, and as a result, the energy density of the negative electrode and the lithium battery can be improved.

[0094] [Negative electrode layer: first inactive member] 4 to 5 and 8 to 12, the all-solid-state secondary battery 1 may further include a first inactive member 40, 40a, 40b disposed on at least one of the other surface of the negative electrode current collector 21 and the other surface of the positive electrode current collector 11.

[0095] The first inactive members 40, 40a, and 40b do not contain a positive electrode active material. The first inactive members 40, 40a, and 40b may be, for example, an insulating member.

[0096] The first inactive members 40, 40a, 40b may be electrically conductive by additionally including a conductive material, or may be, for example, a flame-retardant inactive member by additionally including a flame-retardant material.

[0097] The first inactive members 40, 40a, 40b may be, for example, elastic members. The first inactive members 40, 40a, 40b may be, for example, porous elastic members. The first inactive members 40, 40a, 40b may be, for example, elastic members having one or more of porosity, conductivity, and flame retardancy.

[0098] The first inactive members 40, 40a, 40b provide a buffer function to the all-solid-state secondary battery 1. The first inactive members 40, 40a, 40b provide, for example, stress relaxation and restoring force. The first inactive members 40, 40a, 40b can effectively accommodate the volume change of the all-solid-state secondary battery 1 and apply a certain pressure to the all-solid-state secondary battery 1.

[0099] The first inactive members 40, 40a, 40b have, for example, a lower elastic modulus than the negative electrode current collector 21. Since the first inactive members 40, 40a, 40b have a lower elastic modulus than the negative electrode current collector 21, they can more effectively accommodate the volume change of the negative electrode layer 20 during charging and discharging of the all-solid-state secondary battery 1. The first inactive members 40, 40a, 40b can effectively relieve internal stress caused by the volume change of the all-solid-state secondary battery 1 during charging and discharging of the all-solid-state secondary battery 1, thereby improving the cycle characteristics of the all-solid-state secondary battery 1.

[0100] The first inactive members 40, 40a, 40b may be disposed, for example, on the negative electrode layer 20 of the all-solid-state secondary battery 1. When the volume change of the negative electrode layer 20 is relatively large compared to the positive electrode layer 10 and the solid electrolyte layer 30 during charging and discharging of the all-solid-state secondary battery 1, the first inactive members 40, 40a, 40b are disposed adjacent to the negative electrode layer 20, so that the volume change of the negative electrode layer 20 can be more effectively accommodated. In addition, the first inactive members 40, 40a, 40b can apply a certain pressure to the negative electrode layer 20, so that, for example, uniform deposition of lithium metal can be induced in the negative electrode layer 20. Therefore, the generation of defects in the all-solid-state secondary battery 1 due to non-uniform deposition of lithium metal can be more effectively prevented.

[0101] In another embodiment, the first inactive member 40, 40a, 40b may be disposed, for example, on the positive electrode layer 10 of the all-solid-state secondary battery 1. By disposing the first inactive member 40, 40a, 40b adjacent to the positive electrode layer 10, the volume change of the all-solid-state secondary battery 1 can be more effectively accommodated. In addition, the first inactive member 40, 40a, 40b applies a certain pressure to the all-solid-state secondary battery 1, thereby inducing, for example, uniform deposition of lithium metal in the negative electrode layer 20. Therefore, the generation of defects in the all-solid-state secondary battery 1 due to non-uniform deposition of lithium metal can be more effectively prevented or reduced.

[0102] The first inactive members 40, 40a, 40b may include a polymer material, a rubber material, or a combination thereof. The first inactive members 40, 40a, 40b may have stress relaxation and restoring force by including a polymer material, a rubber material, or a combination thereof. The polymer material may include, for example, a polyurethane-based polymer, a polyacrylic-based polymer, a polystyrene-based polymer, a polyester-based polymer, a polyamide-based polymer, a polyolefin-based polymer, or a combination thereof. The polymer material may be, for example, a polymer resin. The polymer material may be, for example, an adhesive resin. The rubber material may include, for example, natural rubber (NR), butadiene rubber (BR), nitrile rubber, silicone rubber, isoprene rubber (IR), styrene-butadiene rubber (SBR), isoprene-butadiene rubber, styrene-isoprene-butadiene rubber, acrylonitrile-butadiene rubber (NBR), ethylene-propylene-diene rubber, halogenated butyl rubber, chloroprene (CR), halogenated isoprene rubber, halogenated isobutylene copolymer, chloroprene rubber, butyl rubber (IIR), halogenated isobutylene-p-methylstyrene rubber, or combinations thereof. The polyurethane-based polymer may include, for example, polyester-based polyurethane, polyether-based polyurethane, or combinations thereof. The polyacrylic-based polymer may include, for example, polyacrylate, polymethylacrylate, polymethacrylate, polymethylmethacrylate, or combinations thereof. The polystyrene-based polymer may include, for example, styrene-ethylene-butylene copolymer (SEB), styrene-butadiene-styrene copolymer (SBS), hydrogenated products of SBS (styrene-ethylene-butylene-styrene copolymer (SEBS)), styrene-isoprene-styrene copolymer (SIS), hydrogenated products of SIS (styrene-ethylene-propylene-styrene copolymer (SEPS)), styrene-isobutylene-styrene copolymer (SIBS), styrene-butadiene-styrene-butadiene (SBSB), styrene-butadiene-styrene-butadiene-styrene (SBSBS), polystyrene (PS), acrylonitrile-styrene copolymer (AS), acrylonitrile-butadiene-styrene copolymer (ABS), or combinations thereof.The polyester-based polymer may include, for example, polyethylene terephthalate, polybutylene terephthalate, or a combination thereof. The polyamide-based polymer may include, for example, polyamide 6, polyamide 11, polyamide 12, polyamide 66, polyamide 610, or a combination thereof. The polyolefin-based polymer may include, for example, polyethylene, polypropylene, ethylene propylene copolymer, propylene-1-hexene copolymer, propylene-4-methyl-1-pentene copolymer, propylene-1-butene copolymer, ethylene-1-hexene copolymer, ethylene-4-methyl-pentene copolymer, ethylene-1-butene copolymer, 1-butene-1-hexene copolymer, 1-butene-4-methyl-pentene, ethylene methacrylic acid copolymer, ethylene ethyl methacrylate copolymer, ethylene ethyl methacrylate copolymer, ethylene butyl methacrylate copolymer. The polyolefin may include, for example, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, propylene-methacrylic acid copolymer, propylene-methyl methacrylate copolymer, propylene-ethyl methacrylate copolymer, propylene-butyl methacrylate copolymer, propylene-methyl acrylate copolymer, propylene-ethyl acrylate copolymer, propylene-butyl acrylate copolymer, ethylene-vinyl acetate copolymer (EVA), propylene-vinyl acetate copolymer, or combinations thereof.

[0103] The first inactive member 40, 40a, 40b may include, for example, a porous foam, a porous sponge, or a combination thereof. The first inactive member 40, 40a, 40b may include, for example, a porous foam sheet, a porous sponge sheet, or a combination thereof. The first inactive member 40, 40a, 40b may have such a form, so that it can simultaneously provide porosity and a cushioning function. The porous foam may include, for example, a closed cell, an open cell, or a combination thereof. The porous sponge may include, for example, a closed cell, an open cell, or a combination thereof. The closed cell means, for example, a cell or pore that is not connected to the surrounding atmosphere as a closed pore. The open cell means, for example, a cell or pore that is connected to the surrounding atmosphere as an open pore. The first inactive member 40, 40a, 40b may, for example, comprise a closed cell porous foam, an open cell porous foam, a closed cell porous sponge, an open cell porous sponge, or a combination thereof. The porous foam may, for example, comprise both closed cells and open cells (e.g., simultaneously). The porous sponge may, for example, comprise both closed cells and open cells (e.g., simultaneously).

[0104] The first inactive member 40, 40a, 40b may include, for example, a conductive material. The conductive material may be, for example, graphite, carbon black, acetylene black, Ketjen black, Denka black, carbon fiber, carbon nanotube (CNT), graphene, metal fiber, metal powder, etc. The content of the conductive material included in the first inactive member 40, 40a, 40b may be, for example, 1 to 30 parts by weight, 1 to 20 parts by weight, 1 to 15 parts by weight, 1 to 10 parts by weight, 5 to 40 parts by weight, 5 to 30 parts by weight, or 5 to 35 parts by weight, based on 100 parts by weight of the first inactive member 40, 40a, 40b. Since the first inactive member 40, 40a, 40b has conductivity (for example, is a conductor), the first inactive member 40, 40a, 40b may serve as a negative electrode current collector.

[0105] The first inactive member 40, 40a, 40b includes, for example, a matrix and a filler. The matrix includes, for example, a base material and a reinforcing material. The matrix includes, for example, a fibrous base material and a fibrous reinforcing material. When the matrix includes the fibrous base material, the matrix can have elasticity. The fibrous base material includes, for example, one or more selected from pulp fiber, insulating polymer fiber, and ion-conductive polymer fiber. When the matrix includes the reinforcing material, the strength of the matrix is ​​improved. The fibrous reinforcing material is, for example, glass fiber, metal oxide fiber, ceramic fiber, etc. The fibrous reinforcing material is, for example, a flame retardant material. The filler is, for example, a moisture getter and / or a flame retardant. The filler is, for example, a metal hydroxide having moisture adsorption properties. The metal hydroxide contained in the filler is, for example, Mg(OH)2, Fe(OH)3, Sb(OH)3, Sn(OH)4, Ti(OH)3, Zr(OH)4, Al(OH)3, or a combination thereof.

[0106] The thickness of the first inactive member 40, 40a, 40b is, for example, thicker than the thickness of the first negative electrode active material layer 22. The first inactive member 40, 40a, 40b has a thickness thicker than the first negative electrode active material layer 22, so that the volume change of the negative electrode layer 20 during charging and discharging can be more effectively accommodated. The thickness of the first negative electrode active material layer 22 is 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the thickness of the first inactive member 40, 40a, 40b. The thickness of the first negative electrode active material layer 22 is, for example, 1% to 50%, 1% to 40%, 1% to 30%, 1% to 20%, or 1% to 10% of the thickness of the first inactive member 40, 40a, 40b. The thickness of the first inactive member 40, 40a, 40b is, for example, 10 μm to 300 μm, 20 μm to 300 μm, 50 μm to 300 μm, or 100 μm to 200 μm. If the thickness of the first inactive member 40, 40a, 40b is excessively thin, it is difficult to provide the intended effect, and if the thickness of the first inactive member 40, 40a, 40b is excessively thick, the energy density of the all-solid-state secondary battery 1 may be reduced. The shape of the first inactive member 40, 40a, 40b is not particularly limited and may be selected according to the shape of the all-solid-state secondary battery 1. The first inactive member 40, 40a, 40b may be, for example, in the form of a sheet, a rod, or a gasket. In other embodiments, the first inactive member 40, 40a, 40b may be omitted.

[0107] [Positive electrode layer] [Cathode layer: Cathode active material] 1 to 12, the positive electrode active material layer 12 contains, for example, a positive electrode active material.

[0108] The positive electrode active material contained in the positive electrode active material layer 12 is a positive electrode active material that can reversibly absorb and desorb lithium ions. The positive electrode active material includes, for example, an oxide-based positive electrode active material, a sulfide-based positive electrode active material, or a combination thereof.

[0109] The oxide-based positive electrode active material includes, for example, lithium transition metal oxide, metal oxide, or a combination thereof. The lithium transition metal oxide includes, for example, lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminium oxide, lithium nickel cobalt mangense oxide, lithium manganate, lithium iron phosphate, or a combination thereof. The lithium oxide includes, for example, iron oxide, vanadium oxide, or a combination thereof.

[0110] Sulfide-based positive electrode active materials include, for example, nickel sulfide, copper sulfide, Li2S, Li2S-containing complexes, or combinations thereof.

[0111] The oxide-based positive electrode active material can be, for example, one or more composite oxides of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof. The lithium-containing oxide-based positive electrode active material can be, for example, Li a A 1-b B' b D2 (wherein 0.90≦a≦1, and 0≦b≦0.5); Li a E 1-b B' b O 2-c D c (In the above formula, 0.90≦a≦1, 0≦b≦0.5, and 0≦c≦0.05.) 2-b B' b O 4-c D c (In the above formula, 0≦b≦0.5, 0≦c≦0.05.); Lia Ni 1-b-c Co b B' c D α (In the above formula, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2.); Li a Ni 1-b-c Co b B' c O 2-α F' α (In the above formula, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2.); Li a Ni 1-b-c Co b B' c O 2-α F' α (In the above formula, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2.); Li a Ni 1-b-c Mn b B' c D α (In the above formula, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2.); Li a Ni 1-b-c Mn b B' c O 2-α F' α (In the above formula, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2.); Li a Ni 1-b-c Mn b B' c O 2-α F' α (In the above formula, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2.); Li a Ni b E c G d O2 (wherein, 0.90≦a≦1, 0≦b≦0.9, 0≦c≦0.5, 0.001≦d≦0.1); Li a Ni b Co c Mn d G eO2 (wherein, 0.90≦a≦1, 0≦b≦0.9, 0≦c≦0.5, 0≦d≦0.5, 0.001≦e≦0.1); Li a NiG b O2 (wherein 0.90≦a≦1, 0.001≦b≦0.1); Li a CoG b O2 (wherein 0.90≦a≦1, 0.001≦b≦0.1); Li a MnG b O2 (wherein 0.90≦a≦1, 0.001≦b≦0.1); Li a Mn2G b O4 (wherein 0.90≦a≦1, 0.001≦b≦0.1); LiV2O5; LiI'O2; LiNiVO4; Li (3-f) J2(PO4)3(0≦f≦2);Li (3-f) It may include a compound represented by any one of the chemical formulas Fe2(PO4)3(0≦f≦2);LiFePO4.

[0112] In the chemical formula expressing the above-mentioned compound, A is Ni, Co, Mn, or a combination thereof, B' is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof, D is O, F, S, P, or a combination thereof, E is Co, Mn, or a combination thereof, F' is F, S, P, or a combination thereof, G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof, Q is Ti, Mo, Mn, or a combination thereof, I' is Cr, V, Fe, Sc, Y, or a combination thereof, and J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof. It is also possible to use a compound having a coating layer added to the surface of the above-mentioned compound, and it is also possible to use a mixture of the above-mentioned compound and a compound having a coating layer added thereto. The coating layer added to the surface of the above-mentioned compound includes, for example, a coating element compound such as an oxide, hydroxide, oxyhydroxide, oxycarbonate, or hydroxycarbonate of the coating element of the coating element. The compound forming such a coating layer is amorphous or crystalline. The coating element contained in the coating layer is Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The method of forming the coating layer is selected within a range that does not adversely affect the physical properties of the positive electrode active material. The coating method is, for example, spray coating, immersion, etc. The specific coating method is well understood by those skilled in the art, so a detailed description will be omitted.

[0113] The oxide-based positive electrode active material may include, for example, lithium transition metal oxides represented by the following chemical formulas 1 to 8:

[0114] <Chemical formula 1> Li a Ni x Co y M z O 2-b A b

[0115] In the chemical formula 1, 1.0 ≦ a ≦ 1.2, 0 ≦ b ≦ 0.2, 0.8 ≦ x < 1, 0 ≦ y ≦ 0.3, 0 < z ≦ 0.3, and x + y + z = 1,

[0116] M is manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) or a combination thereof,

[0117] A is F, S, Cl, Br or a combination thereof,

[0118] <Chemical formula 2> LiNi x Co y Mn z O2

[0119] <Chemical formula 3> LiNi x Co y Al z O2

[0120] In the chemical formulas 2 and 3, 0.8 ≦ x ≦ 0.95, 0 ≦ y ≦ 0.2, 0 < z ≦ 0.2 and x + y + z = 1,

[0121] <Chemical formula 4> LiNi x Co y Mn z Al w O2

[0122] In the chemical formula 4, 0.8 ≦ x ≦ 0.95, 0 ≦ y ≦ 0.2, 0 < z ≦ 0.2, 0 < w ≦ 0.2, and x + y + z + w = 1,

[0123] <Chemical formula 5> Li a Co x M y O 2-b A b

[0124] In the chemical formula 5, 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.9 ≤ x ≤ 1, 0 ≤ y ≤ 0.1, and x + y = 1,

[0125] M is manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) or a combination thereof, A is F, S, Cl, Br or a combination thereof,

[0126] <Chemical formula 6> Li a Ni x Mn y M’ z O 2-b A b

[0127] In the chemical formula 6, 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0 < x ≤ 0.3, 0.5 ≤ y < 1, 0 < z ≤ 0.3, and x + y + z = 1,

[0128] M’ is cobalt (Co), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) or a combination thereof,

[0129] A is F, S, Cl, Br or a combination thereof,

[0130] <Chemical formula 7> Li a M1 x M2 y PO 4-b X b

[0131] In the above formula 7, 0.90≦a≦1.1, 0≦x≦0.9, 0≦y≦0.5, 0.9 <x+y<1.1、0≦b≦2であり、

[0132] M1 is chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr) or a combination thereof;

[0133] M2 is magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), zinc (Zn), boron (B), niobium (Nb), gallium (Ga), indium (In), molybdenum (Mo), tungsten (W), aluminum (Al), silicon (Si), chromium (Cr), vanadium (V), scandium (Sc), yttrium (Y), or a combination thereof; and X is O, F, S, P, or a combination thereof.

[0134] <Chemical formula 8> Li a M3 z PO4

[0135] In the above Chemical Formula 8, 0.90≦a≦1.1 and 0.9≦z≦1.1;

[0136] M3 is chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr), or a combination thereof.

[0137] The oxide-based positive electrode active material may be covered with a coating layer. The coating layer may be any known coating layer for a positive electrode active material of an all-solid-state secondary battery. The coating layer may be, for example, Li2O-ZrO2 (LZO).

[0138] The size of the oxide-based positive electrode active material may be, for example, 0.1 to 30 μm, 0.5 to 20 μm, or 1 to 15 μm. The oxide-based positive electrode active material may be, for example, single crystal particles or polycrystalline particles.

[0139] The sulfide-based positive electrode active material may include, for example, a Li2S-containing composite. The Li2S-containing composite may include, for example, a composite of Li2S and carbon, a composite of Li2S and carbon and a solid electrolyte, a composite of Li2S and a solid electrolyte, a composite of Li2S and a lithium salt, a composite of Li2S and a lithium salt and carbon, a composite of Li2S and a metal carbide, a composite of Li2S and carbon and a metal carbide, a composite of Li2S and a metal nitride, a composite of Li2S and carbon and a metal nitride, or a combination thereof.

[0140] The Li2S and carbon composite includes carbon. Carbon is, for example, a material containing carbon atoms, and any material used as a conductive material in the art can be used. Carbon can be, for example, crystalline carbon, amorphous carbon, or a combination thereof. Carbon can be, for example, a calcined product of a carbon precursor. Carbon can be, for example, a carbon nanostructure. Carbon nanostructures can be, for example, one-dimensional carbon nanostructures, two-dimensional carbon nanostructures, three-dimensional carbon nanostructures, or a combination thereof. Carbon nanostructures can be, for example, carbon nanotubes, carbon nanofibers, carbon nanobelts, carbon nanorods, graphene, graphene oxide (GO), reduced graphene oxide (rGO), graphene balls (GB), or a combination thereof. Carbon can be, for example, porous carbon or non-porous carbon. Porous carbon can include, for example, periodic and regular two-dimensional or three-dimensional pores. The porous carbon may be, for example, carbon black such as Ketjen Black, Acetylene Black, Denka Black, Thermal Black, Channel Black, etc.; graphite, activated carbon, or a combination thereof. The form of carbon may be, for example, particulate, sheet, fibrous, etc., and is not limited thereto, and any method used in the art for carbon can be used. The method for producing a composite of Li2S and carbon may be, for example, a dry method, a wet method, or a combination thereof, and is not limited thereto, and the method for producing a composite of Li2S and carbon in the art is, for example, milling, heat treatment, vapor deposition, etc., but is not necessarily limited thereto, and any method used in the art can be used.

[0141] The composite of Li2S, carbon, and a solid electrolyte includes carbon and a solid electrolyte. Carbon refers to the composite of Li2S and carbon described above. The solid electrolyte can be any of those used as ion-conducting materials in the technical field, for example, as an amorphous solid electrolyte. The solid electrolyte can be, for example, an inorganic solid electrolyte. The solid electrolyte can be, for example, a crystalline solid electrolyte, an amorphous solid electrolyte, or a combination thereof. The solid electrolyte can be, for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, or a combination thereof. The sulfide-based solid electrolyte can include, for example, Li, S, and P, and can further include a halogen element selectively. The sulfide-based solid electrolyte can be selected from the sulfide-based solid electrolytes used in the solid electrolyte layer. The sulfide-based solid electrolyte can be, for example, 1×10 -5 S / cm or more. Examples of sulfide-based solid electrolytes include Li3PO4-Li2SO4, Li2S-P2S5, Li2S-P2S5-LiX (X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (m and n are positive numbers, Z is one of Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (p, q are positive numbers, M is one of P, Si, Ge, B, Al, GaIn), Li 7-x P.S. 6-x Cl x (0≦x≦2),Li 7-x P.S. 6-x Br x (0≦x≦2), and Li 7-x P.S. 6-x I x (0≦x≦2). The oxide-based solid electrolyte may include, for example, Li, O, and a transition metal element, and may further include other elements selectively. The oxide-based solid electrolyte may have a specific surface area of ​​1×10-5 The solid electrolyte may have an ionic conductivity of 100 S / cm or more. The oxide-based solid electrolyte may be selected from oxide-based solid electrolytes used in the solid electrolyte layer. The solid electrolyte may be, for example, a mixture of a sulfide-based solid electrolyte and a lithium salt. For example, it may be a mixture of Li3PO4-Li2SO4 and a binary lithium salt or a mixture of Li3PO4-Li2SO4 and a ternary lithium salt.

[0142] The composite of Li2S and a solid electrolyte includes a solid electrolyte, which is understood with reference to the composite of Li2S, carbon, and a solid electrolyte described above.

[0143] The complex of Li2S and a lithium salt includes a lithium salt compound. The lithium salt compound does not include, for example, a sulfur (S) atom. The lithium salt compound may be, for example, a binary compound consisting of lithium and one element selected from Groups 13 to 17 of the periodic table. The binary compound may include, for example, one or more selected from LiF, LiCl, LiBr, LiI, LiH, Li2S, Li2O, Li2Se, Li2Te, Li3N, Li3P, Li3As, Li3Sb, LiI3, and LiB3. The lithium salt compound may be, for example, a ternary compound consisting of lithium and two elements selected from Groups 13 to 17 of the periodic table. The ternary compound includes, for example, one or more selected from Li3OCl, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiNO3, Li2CO3, LiBH4, Li2SO4, Li3BO3, Li3PO4, Li4NCl, Li5NCl2, and Li3BN2. The lithium salt compound is in particular one or more lithium halide compounds selected from LiF, LiCl, LiBr, and LiI. The composite of Li2S and a solid electrolyte includes a solid electrolyte. The solid electrolyte refers to the solid electrolyte used in the composite of Li2S, carbon, and a solid electrolyte described above. The complex of Li2S and the solid electrolyte includes, for example, a complex of Li2S and one or more lithium salts selected from LiF, LiCl, LiBr, LiI, LiH, Li2S, Li2O, Li2Se, Li2Te, Li3N, Li3P, Li3As, Li3Sb, LiI3, and LiB3.

[0144] The complex of Li2S, a lithium salt and carbon includes a lithium salt compound and carbon, the carbon being understood with reference to the complex of Li2S and carbon described above.

[0145] The composite of Li2S and metal carbide includes a metal carbide. The metal carbide is, for example, a two-dimensional metal carbide. The two-dimensional metal carbide is, for example, MXene. The two-dimensional metal carbide is, for example, M n+1 C n T x(M is a transition metal, T is an end group, T is O, OH and / or F, n=1, 2 or 3, x is the number of end groups). Two-dimensional metal carbides are, for example, Ti2CT x , (Ti 0.5 , Nb 0.5 )2CT x , Nb2CT x , V2CT x , Ti3C2T x , (V 0.5 , Cr 0.5 )3C2T x , Ti3CNT x , Ta4C3T x , Nb4C3T x or a combination thereof. The surface of the two-dimensional metal carbide is terminated with O, OH and / or F.

[0146] The composite of Li2S, carbon and metal carbide includes carbon and metal carbide, carbon refers to the composite of Li2S and carbon described above, and metal carbide refers to the composite of Li2S and metal carbide described above.

[0147] The complex of Li2S and a metal nitride includes a metal nitride. The metal nitride is, for example, a two-dimensional metal nitride. The two-dimensional metal nitride is, for example, M n+1 N n T x (M is a transition metal, T is an end group, T is O, OH and / or F, n=1, 2 or 3, x is the number of end groups). The surface of the two-dimensional metal nitride is terminated with O, OH and / or F.

[0148] The complex of Li2S, carbon and metal nitride includes carbon and metal nitride, carbon refers to the complex of Li2S and carbon described above, and metal carbide refers to the complex of Li2S and metal nitride described above.

[0149] The Li2S-containing composite may further include, for example, a second fibrous sulfide-based solid electrolyte (not shown). The Li2S-containing composite may be a composite of Li2S and the second fibrous sulfide-based solid electrolyte, or a composite of Li2S and the second fibrous sulfide-based solid electrolyte and the above-mentioned carbon, solid electrolyte, lithium salt, metal carbide, or metal nitride.

[0150] By further including the second fibrous sulfide-based solid electrolyte in the Li2S-containing composite, the deterioration of the lithium battery can be further suppressed, and the cycle characteristics of the lithium battery can be further improved. The size of the second fibrous sulfide-based solid electrolyte is also smaller than the size of the first fibrous sulfide-based solid electrolyte 100. The length and / or thickness of the second fibrous sulfide-based solid electrolyte may be 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the length and / or thickness of the first fibrous sulfide-based solid electrolyte 100, respectively. The length and / or thickness of the second fibrous sulfide-based solid electrolyte may be 0.1 to 50%, 0.5 to 40%, 1 to 30%, 1 to 20%, or 1 to 10% of the length and / or thickness of the first fibrous sulfide-based solid electrolyte 100, respectively. The second fibrous sulfide-based solid electrolyte has the same form as the first fibrous sulfide-based solid electrolyte 100, and is also smaller, for example. The second fibrous sulfide-based solid electrolyte may have such a reduced length and / or thickness so that it can be easily distributed within the Li2S-containing composite. The second fibrous sulfide-based solid electrolyte may have such a reduced length and / or thickness so that the deterioration of the lithium battery may be further suppressed and the cycle characteristics of the lithium battery may be further improved.

[0151] The size of the sulfide-based positive electrode active material may be, for example, 0.1 to 50 μm, 0.5 to 30 μm, 0.5 to 20 μm, or 1 to 10 μm. The size of Li2S may be, for example, 1 nm to 10 μm, 10 nm to 5 μm, 10 nm to 3 μm, or 10 nm to 1 μm. The size of the Li2S-containing composite may be, for example, 0.1 to 50 μm, 0.5 to 30 μm, 0.5 to 20 μm, or 1 to 10 μm.

[0152] The shape of the positive electrode active material is, for example, a particle shape such as a perfect sphere or an oval sphere. The particle size of the positive electrode active material is not particularly limited and is within a range applicable to positive electrode active materials of conventional all-solid-state secondary batteries. The content of the positive electrode active material in the positive electrode layer 10 is also not particularly limited and is within a range applicable to positive electrode layers of conventional all-solid-state secondary batteries. The content of the positive electrode active material in the positive electrode active material layer 12 may be, for example, 10 wt% to 99 wt%, 10 wt% to 90 wt%, 10 wt% to 80 wt%, 10 wt% to 70 wt%, or 10 wt% to 50 wt% of the total weight of the positive electrode active material layer 12.

[0153] [Positive electrode layer: solid electrolyte] The positive electrode active material layer 12 may further include, for example, a solid electrolyte. The solid electrolyte may be, for example, a sulfide-based solid electrolyte. The solid electrolyte included in the positive electrode layer 10 may be the same as or different from the solid electrolyte included in the solid electrolyte layer 30. Details related to the solid electrolyte may be understood with reference to the solid electrolyte layer 30.

[0154] The solid electrolyte contained in the positive electrode active material layer 12 may have a smaller D50 average particle diameter than the solid electrolyte contained in the solid electrolyte layer 30. For example, the D50 average particle diameter of the solid electrolyte contained in the positive electrode active material layer 12 may be 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, or 20% or less of the D50 average particle diameter of the solid electrolyte contained in the solid electrolyte layer 30. The D50 average particle diameter is, for example, a median diameter (D50). The median diameter (D50) is, for example, a particle size corresponding to a 50% cumulative volume calculated from the particle side having a small particle size in a particle size distribution measured by a laser diffraction method.

[0155] The solid electrolyte content in the positive electrode active material layer 12 may be, for example, 1 wt % to 40 wt %, 1 wt % to 30 wt %, 1 wt % to 20 wt %, or 1 wt % to 10 wt % of the total weight of the positive electrode active material layer 12.

[0156] [Positive electrode layer: conductive material] The positive electrode active material layer 12 may further include a conductive material. The conductive material may be, for example, a carbon-based conductive material, a metal-based conductive material, or a combination thereof. The carbon-based conductive material may be, for example, graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or a combination thereof, and is not limited thereto, and any material used as a carbon-based conductive material in the relevant technical field may be used. The metal-based conductive material may be, for example, metal powder, metal fiber, or a combination thereof, and is not limited thereto, and any material used as a metal-based conductive material in the relevant technical field may be used. The conductive material content of the positive electrode active material layer 12 may be, for example, 1 wt% to 30 wt%, 1 wt% to 20 wt%, or 1 wt% to 10 wt% of the total weight of the positive electrode active material layer 12.

[0157] [Positive electrode layer: binder] The positive electrode active material layer 12 may further include a binder. The binder may be, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, or the like, but is not limited thereto, and any binder used as a binder in the relevant technical field may be used. The content of the binder contained in the positive electrode active material layer 12 may be, for example, 1 wt % to 10 wt % of the total weight of the positive electrode active material layer 12. The binder may be omitted.

[0158] [Positive electrode layer: Other additives] The positive electrode active material layer 12 may further contain additives such as a filler, a coating agent, a dispersant, and an ion-conductive assistant in addition to the above-mentioned positive electrode active material, solid electrolyte, binder, and conductive material.

[0159] As the filler, coating agent, dispersant, ion-conductive assistant, and the like contained in the positive electrode active material layer 12, known materials generally used for electrodes of all-solid-state secondary batteries can be used.

[0160] [Dry positive electrode: positive electrode current collector] The positive electrode current collector 11 is, for example, a plate or foil made of indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The positive electrode current collector 11 can be omitted. The thickness of the positive electrode current collector 11 is, for example, 1 μm to 100 μm, 1 μm to 50 μm, 5 μm to 25 μm, or 10 μm to 20 μm.

[0161] The positive electrode current collector 11 may include, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The base film may be, for example, an insulator. When the base film includes an insulating thermoplastic polymer, the base film is softened or liquefied in the event of a short circuit, thereby cutting off the operation of the battery and suppressing a sudden increase in current. The metal layer may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), or an alloy thereof. The metal layer acts as an electrochemical fuse and is cut off in the event of an overcurrent to perform a short circuit prevention function. The limiting current and maximum current can be adjusted by adjusting the thickness of the metal layer. The metal layer can be electrodeposited or vapor-deposited on the base film. If the thickness of the metal layer is thin, the limiting current and / or maximum current of the positive electrode current collector 11 is reduced, and the stability of the lithium battery during a short circuit can be improved. A lead tab can be added to the metal layer for connection to the outside. The lead tab can be welded to the metal layer or the metal layer / base film laminate by ultrasonic welding, laser welding, spot welding, or the like. During welding, the base film and / or the metal layer can be melted and the metal layer can be electrically connected to the lead tab. To further strengthen the welding between the metal layer and the lead tab, a metal chip can be added between the metal layer and the lead tab. The metal chip can be a thin piece of the same material as the metal of the metal layer. The metal chip can be, for example, a metal foil, a metal mesh, or the like. The metal chip can be, for example, an aluminum foil, a copper foil, a SUS foil, or the like.After disposing the metal piece on the metal layer, the lead tab may be welded to the metal piece / metal layer laminate or metal piece / metal layer / base film laminate. During welding, the base film, metal layer, and / or metal piece may melt, and the metal layer or metal layer / metal piece laminate may be electrically connected to the lead tab. A metal piece and / or a lead tab may be added to a portion on the metal layer. The thickness of the base film may be, for example, 1 to 50 μm, 1.5 to 50 μm, 1.5 to 40 μm, or 1 to 30 μm. When the base film has a thickness in such a range, the weight of the positive electrode assembly may be more effectively reduced. The melting point of the base film may be, for example, 100 to 300° C., 100 to 250° C., or 100 to 200° C. When the base film has a melting point in such a range, the base film may melt during the process of welding the lead tab, and may be easily bonded to the lead tab. In order to improve the adhesive strength between the base film and the metal layer, a surface treatment such as a corona treatment may be performed on the base film. The thickness of the metal layer may be, for example, 0.01 to 3 μm, 0.1 to 3 μm, 0.1 to 2 μm, or 0.1 to μm. When the metal layer has a thickness in such a range, the stability of the positive electrode assembly can be ensured while maintaining the conductivity. The thickness of the metal piece may be, for example, 2 to 10 μm, 2 to 7 μm, or 4 to 6 μm. When the metal piece has a thickness in such a range, the connection between the metal layer and the lead tab can be more easily performed. When the positive electrode current collector 11 has such a structure, the weight of the positive electrode can be reduced, and as a result, the energy density of the positive electrode and the all-solid-state secondary battery can be improved.

[0162] [Positive electrode layer: first inactive material] 4, 5, and 8 to 12, the all-solid-state secondary battery 1 may further include a first inactive member 40, 40a, 40b disposed on at least one of the other surface of the negative electrode current collector 21 and the other surface of the positive electrode current collector 11 (e.g., one or both (e.g., opposite) surfaces).

[0163] Further details regarding the first inactive members 40a, 40a, 40b can be understood with reference to the first inactive members 40, 40a, 40b of the negative electrode layer described above.

[0164] [Positive electrode layer: second inactive material] 6 to 12, the positive electrode layer 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on one surface (e.g., one or both (e.g., opposite) surfaces) of the positive electrode current collector 11. A second inactive member 50 is disposed on one surface (e.g., one or both (e.g., opposite) surfaces) of the positive electrode layer 10.

[0165] 7, 9, and 11, the second inactive member 50 is disposed on one side of the positive electrode active material layer 12 and disposed between the solid electrolyte layer 30 and the positive electrode current collector 11 facing the solid electrolyte layer 30. The second inactive member 50 is not disposed on one side of the positive electrode current collector 11. Referring to FIGS. 6, 8, 10, and 12, the second inactive member 50 is disposed on one side of the positive electrode active material layer 12 and the positive electrode current collector 11. By including the second inactive member 50, cracks in the solid electrolyte layer 30 are prevented during the manufacture of the all-solid-state secondary battery 1 and / or during charging and discharging, and as a result, the cycle characteristics of the all-solid-state secondary battery 1 are improved. In the all-solid-state secondary battery 1 that does not include the second inactive member 50, uneven pressure is applied to the solid electrolyte layer 30 that contacts the positive electrode layer 10 during the manufacture of the all-solid-state secondary battery 1 and / or during charging and discharging, causing cracks in the solid electrolyte layer 30, which increases the possibility of short circuiting due to the growth of lithium metal.

[0166] 6 to 12, in the all-solid-state secondary battery 1, the thickness of the second inactive member 50 is, for example, thicker than the thickness of the first negative electrode active material layer 22. The thickness of the second inactive member 50 is, for example, thicker than the thickness of the solid electrolyte layer 30.

[0167] 6 to 12, the second inactive member 50 surrounds the side of the positive electrode layer 10 and contacts the solid electrolyte layer 30. The second inactive member 50 surrounds the side of the positive electrode layer 10 and contacts the solid electrolyte layer 30, thereby effectively suppressing cracks in the solid electrolyte layer 30 that occur due to a pressure difference during a press process from the solid electrolyte layer 30 that is not in contact with the positive electrode layer 10. The second inactive member 50 surrounds the side of the positive electrode layer 10 and is separated from the negative electrode layer 20, more specifically, the first negative electrode active material layer 22. The second inactive member 50 surrounds the side of the positive electrode layer 10 and contacts the solid electrolyte layer 30, and is separated from the negative electrode layer 20. Therefore, the physical contact between the positive electrode layer 10 and the first negative electrode active material layer 22 suppresses the occurrence of a short circuit or the occurrence of a short circuit due to overcharging of lithium. By disposing the second inactive member 50 simultaneously on one side of the positive electrode active material layer 12 and the positive electrode current collector 11, the possibility of a short circuit occurring due to contact between the positive electrode current collector 11 and the negative electrode layer 20 is more effectively suppressed.

[0168] 6 to 12, the second inactive member 50 extends from one side of the positive electrode layer 10 to an end of the solid electrolyte layer 30. The second inactive member 50 extends to the end of the solid electrolyte layer 30, thereby suppressing cracks occurring at the end of the solid electrolyte layer 30. The end of the solid electrolyte layer 30 is the outermost part that contacts the side of the solid electrolyte layer 30. The second inactive member 50 extends to the outermost part that contacts the side of the solid electrolyte layer 30. The second inactive member 50 is separated from the negative electrode layer 20, more specifically, the first negative electrode active material layer 22. The second inactive member 50 extends to the end of the solid electrolyte layer 30 but does not contact the negative electrode layer 20. The second inactive member 50 fills a space that extends from one side of the positive electrode layer 10 to the end of the solid electrolyte layer 30, for example.

[0169] The area of ​​the positive electrode active material layer 12 or the positive electrode layer 10 is smaller than the area of ​​the first negative electrode active material layer 22 or the negative electrode layer 20. The area of ​​the positive electrode active material layer 12 or the positive electrode layer 10 is also smaller than the area of ​​the solid electrolyte layer 30.

[0170] The second inactive member 50 may be, for example, a gasket. By using a gasket as the second inactive member 50, cracks in the solid electrolyte layer 30 caused by a pressure difference during a pressing process can be effectively suppressed.

[0171] The second inactive member 50 has, for example, a single-layer structure. In another embodiment, although not shown in the drawings, the second inactive member 50 may have a multi-layer structure. The multi-layer structure may have, for example, a two-layer, three-layer, or four-layer structure, and by having a multi-layer structure, the physical properties of the second inactive member 50 may be more precisely adjusted.

[0172] Although not shown in the drawings, a part or the whole of the second inactive member 50 may be arranged spaced apart from the side of the positive electrode active material layer 12. By arranging a part or the whole of the second inactive member 50 spaced apart from the side of the positive electrode active material layer 12, the manufacturing process of the all-solid-state secondary battery 1 may be further facilitated and the manufacturing speed of the all-solid-state secondary battery 1 may be increased. By arranging a part or the whole of the second inactive member 50 spaced apart from the side of the positive electrode active material layer 12, the volume change in the lateral direction of the positive electrode active material layer 12 during charging and discharging may be more effectively required, and the life characteristics of the all-solid-state secondary battery 1 may be further improved. The distance between the second inactive member 50 and the side of the positive electrode active material layer 12 may be, for example, 0.1 μm to 10 mm, 1 μm to 1 mm, 1 μm to 500 μm, 1 μm to 100 μm, 1 μm to 50 μm, or 1 μm to 10 μm, independently of each other.

[0173] 1 to 12, the second inactive member 50 may be selected from the materials used for the first inactive members 40, 40a, and 40b described above. The second inactive member 50 does not include a positive electrode active material. The second inactive member 50 may be, for example, a flame-retardant inactive member, an electronically insulating inactive member, an ionically insulating inactive member, or an elastic inactive member.

[0174] [Solid electrolyte layer] [Solid electrolyte layer: solid electrolyte] 1 to 12, the all-solid-state secondary battery 1 includes a solid electrolyte layer 30 disposed between a positive electrode layer 10 and a negative electrode layer 20. The solid electrolyte layer 30 includes, for example, a solid electrolyte or a combination of a solid electrolyte and a gel electrolyte.

[0175] The solid electrolyte may include, for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a polymer solid electrolyte, or a combination thereof.

[0176] The solid electrolyte is, for example, a sulfide-based solid electrolyte. Examples of the sulfide-based solid electrolyte include Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n (m and n are positive numbers, Z is one of Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (p, q are positive numbers, M is one of P, Si, Ge, B, Al, GaIn), Li 7-x P.S. 6-x Cl x (0≦x≦2), Li 7-x P.S. 6-x Br x (0≦x≦2) and Li 7-x P.S. 6-x I x(0≦x≦2). The sulfide-based solid electrolyte is prepared by processing starting materials such as Li2S and P2S5 by melt quenching or mechanical milling. After such processing, heat treatment can be performed. The solid electrolyte may be amorphous, crystalline, or a mixture thereof. The solid electrolyte may be, for example, one of the above-mentioned sulfide-based solid electrolyte materials that contains at least sulfur (S), phosphorus (P), and lithium (Li) as constituent elements. For example, the solid electrolyte may be a material containing Li2S-P2S5. When a sulfide-based solid electrolyte material containing Li2S-P2S5 is used to form the solid electrolyte, the mixed molar ratio of Li2S and P2S5 is, for example, in the range of Li2S:P2S5=20:80 to 90:10, 25:75 to 90:10, 30:70 to 70:30, or 40:60 to 60:40.

[0177] The sulfide-based solid electrolyte may include, for example, an Argyrodite-type solid electrolyte represented by the following Chemical Formula 1:

[0178] <Chemical formula 1> Li + 12-n-x A n+ X 2- 6-x Y - x

[0179] In the above formula, A is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb, or Ta, X is S, Se, or Te, and Y is Cl, Br, I, F, CN, OCN, SCN, or N3, where 1≦n≦5 and 0≦x≦2. The sulfide-based solid electrolyte is, for example, Li 7-x P.S. 6-x Cl x (0≦x≦2), Li 7-x P.S. 6-x Br x (0≦x≦2) and Li 7-x P.S. 6-x I x(0≦x≦2). The sulfide-based solid electrolyte may be, for example, an Argyrodite-type compound containing one or more selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I.

[0180] The density of the argyrodite-type solid electrolyte may be 1.5 to 2.0 g / cc. When the argyrodite-type solid electrolyte has a density of 1.5 g / cc or more, the internal resistance of the all-solid-state secondary battery is reduced, and penetration of the solid electrolyte layer by Li can be effectively suppressed.

[0181] The oxide-based solid electrolyte is, for example, Li 1+x+y Al x Ti 2-x S y P 3-y O 12 (0 <x<2、0≦y<3)、BaTiO3、Pb(Zr,Ti)O3(PZT)、Pb 1-x La x Zr 1-y Ti y O3(PLZT)(0≦x<1, 0≦y<1), PB(Mg3Nb 2 / 3 )O3-PbTiO3(PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3(0 <x<2、0<y<3)、Li x Al y Ti z (PO4)3(0 <x<2、0<y<1、0<z<3)、Li 1+x+y (Al, Ga) x (Ti, Ge) 2-x S y P 3-y O 12 (0≦x≦1,0≦y≦1), Li x Lay TiO3 (0 < x < 2, 0 < y < 3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O - Al2O3 - SiO2 - P2O5 - TiO2 - GeO2, Li 3+x La3M2O 12 (M = Te, Nb, or Zr, 0 ≦ x ≦ 10), or a combination thereof may be used. The oxide-based solid electrolyte is produced, for example, by a sintering method or the like.

[0182] The oxide-based solid electrolyte is, for example, Li7La3Zr2O 12 (LLZO) and Li 3+x La3Zr 2-a M a O 12 (M doped LLZO, M = Ga, W, Nb, Ta, or Al, 0 < a < 2, 0 ≦ x ≦ 10), which is a garnet-type solid electrolyte selected therefrom.

[0183] The solid polymer electrolyte may, for example, comprise a mixture of a lithium salt and a polymer, or comprise a polymer having an ion-conducting functional group. The solid polymer electrolyte may, for example, be a polymer electrolyte that is in a solid state at 25° C. and 1 atm. The solid polymer electrolyte may, for example, be free of liquid.The polymer solid electrolyte includes a polymer, and the polymer is, for example, polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), poly(styrene-b-ethylene oxide) block copolymer (PS-PEO), poly(styrene-butadiene), poly(styrene-isoprene-styrene), poly(styrene-b-divinylbenzene) block copolymer, poly(styrene-ethylene oxide-styrene) block copolymer, polystyrene sulfonate (PSS), polyvinyl fluoride (PVF, Polyvinyl Fluoride), poly(methylmethacrylate) (PMMA), polyethylene glycol (PEG), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), polyethylenedioxythiophene (PEDOT), polypyrrole (PPY), polyacrylonitrile (PAN), polyaniline, polyacetylene, Nafion, Aquivion, Flemion, Gore, Aciplex, Morgane ADP, sulfonated poly(ether ether ketone), SPEEK, sulfonated poly(arylene ether ketone ketone), SPAEKKS, sulfonated poly(aryl ether ketone), ketone, SPAEK), poly[bis(benzimidazobenzisoquinolinones)], SPBIBI, poly(styrene sulfonate), PSS, and lithium 9,10-diphenylanthracene-2-sulfonate, DPASLi. +) or a combination thereof, but is not limited thereto, and any of those used as a polymer electrolyte in the art can be used. The lithium salt can be any of those used as a lithium salt in the art. Examples of the lithium salt include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (x and y are each 1 to 20), LiCl, LiI, or a mixture thereof. The polymer contained in the polymer solid electrolyte may be, for example, a compound containing 10 or more, 20 or more, 50 or more, or 100 or more repeating units. The weight average molecular weight of the polymer contained in the polymer solid electrolyte may be, for example, 1000 Dalton or more, 10,000 Dalton or more, 100,000 Dalton or more, or 1,000,000 Dalton or more.

[0184] The gel electrolyte is, for example, a polymer gel electrolyte. The gel electrolyte may be, for example, free of polymer and in a gel state.

[0185] The polymer gel electrolyte may, for example, include a liquid electrolyte and a polymer, or an organic solvent and a polymer having an ion-conducting functional group. The polymer gel electrolyte may, for example, be a polymer electrolyte that is in a gel state at 25° C. and 1 atm. The polymer gel electrolyte may, for example, be free of liquid and have a gel state. The liquid electrolyte used in the polymer gel electrolyte may, for example, be a mixture of an ionic liquid, a lithium salt and an organic solvent; a mixture of a lithium salt and an organic solvent; a mixture of an ionic liquid and an organic solvent; or a mixture of a lithium salt, an ionic liquid and an organic solvent. The polymer used in the polymer gel electrolyte may be selected from the polymers used in the solid polymer electrolyte. The organic solvent may be selected from the organic solvents used in the liquid electrolyte. The organic solvent may be, for example, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethylsulfoxide, dioxane, 1,2-dimethoxyethane, sulfolane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or a mixture thereof. The lithium salt may be selected from the lithium salts used in the polymer solid electrolyte. The ionic liquid has a melting point below room temperature, is composed of only ions, and refers to a salt in a liquid state at room temperature or a room temperature molten salt. The ionic liquid may, for example, comprise: a) one or more cations selected from ammonium, pyrrolidinium, pyridinium, pyrimidinium, imidazolinium, piperidinium, pyrazolinium, oxazolinium, pyridazinium, phosphonium, sulfonium, triazolinium, and mixtures thereof; and b) BF4 - , PF6 - , AsF6 - , SbF6 - , AlCl4 -, HSO4 - , ClO4 - , CH3SO3 - , CF3CO2 - , Cl - , Br - , I - , BF4 - , SO4 - , CF3SO3 - , (FSO2)2N - , (C2F5SO2)2N - , (C2F5SO2)(CF3SO2)N - , and (CF3SO2)2N - The polymer solid electrolyte may include one or more compounds containing one or more kinds of anions selected from the above. The polymer solid electrolyte may be impregnated with a liquid electrolyte in a secondary battery to form a polymer gel electrolyte. The polymer gel electrolyte may further include inorganic particles. The polymer contained in the polymer gel electrolyte may be, for example, a compound containing 10 or more, 20 or more, 50 or more, or 100 or more repeating units. The weight average molecular weight of the polymer contained in the polymer gel electrolyte may be, for example, 500 Dalton or more, 1000 Dalton or more, 10,000 Dalton or more, 100,000 Dalton or more, or 1,000,000 Dalton or more.

[0186] [Solid electrolyte layer: binder] The solid electrolyte layer 30 may include, for example, a binder. The binder included in the solid electrolyte layer 30 may be, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited thereto, and any binder used as a binder in the relevant technical field may be used. The binder of the solid electrolyte layer 30 may be the same as or different from the binder included in the positive electrode active material layer 12 and the negative electrode active material layer 22. The binder may be omitted.

[0187] The binder content in the solid electrolyte layer 30 is 0.1 to 10 wt %, 0.1 to 5 wt %, 0.1 to 3 wt %, 0.1 to 1 wt %, 0 to 0.5 wt %, or 0 to 0.1 wt % based on the total weight of the solid electrolyte layer 30.

[0188] In this specification, a substituent is derived from an unsubstituted parent group by replacing one or more hydrogen atoms with other atoms or functional groups. Unless otherwise specified, when a functional group is described as being "substituted", it means that the functional group is substituted with one or more substituents selected from an alkyl group having 1 to 40 carbon atoms, an alkenyl group having 2 to 40 carbon atoms, an alkynyl group having 2 to 40 carbon atoms, a cycloalkyl group having 3 to 40 carbon atoms, a cycloalkenyl group having 3 to 40 carbon atoms, and an aryl group having 7 to 40 carbon atoms. When a functional group is described as being "optionally substituted", it means that the functional group can be substituted with the above-mentioned substituents.

[0189] In the present specification, a and b in "carbon number a to b" refer to the carbon number of a specific functional group. That is, the functional group may contain carbon atoms from a to b. For example, "an alkyl group having 1 to 4 carbon atoms" refers to an alkyl group having 1 to 4 carbons, that is, CH3-, CH3CH2-, CH3CH2CH2-, (CH3)2CH-, CH3CH2CH2CH2-, CH3CH2CH(CH3)-, and (CH3)3C-.

[0190] Nomenclature for a particular radical may include mono-radical or di-radical depending on the context. For example, if a substituent requires two points of attachment to the rest of the molecule, the substituent should be understood to be a diradical. For example, a substituent specified as an alkyl group requiring two points of attachment includes diradicals such as -CH2-, -CH2CH2-, -CH2CH(CH3)CH2-. Other radical nomenclature, such as "alkylene," clearly indicates that the radical is a diradical.

[0191] As used herein, the term "alkyl group" or "alkylene group" refers to an aliphatic hydrocarbon group, branched or unbranched. In one embodiment, the alkyl group is substituted or unsubstituted. The alkyl group includes, but is not limited to, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, hexyl, cyclopropyl, cyclopentyl, cyclohexyl, cycloheptyl, and the like, each of which is optionally substituted or unsubstituted. In one embodiment, the alkyl group has 1-6 carbon atoms. For example, the alkyl group having 1-6 carbon atoms can be, but is not limited to, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, pentyl, 3-pentyl, hexyl, and the like.

[0192] As used herein, the term "alkenyl group" refers to a hydrocarbon group containing 2 to 20 carbon atoms and at least one carbon-carbon double bond, including, but not limited to, ethenyl, 1-propenyl, 2-propenyl, 2-methyl-1-propenyl, 1-butenyl, 2-butenyl, cyclopropenyl, cyclopentenyl, cyclohexenyl, cycloheptenyl, and the like. In one embodiment, the alkenyl group is substituted or unsubstituted. In one embodiment, the alkenyl group can have 2 to 40 carbon atoms.

[0193] As used herein, the term "alkynyl group" refers to a hydrocarbon group containing 2 to 20 carbon atoms and at least one carbon-carbon triple bond, including, but not limited to, ethynyl, 1-propynyl, 1-butynyl, 2-butynyl, and the like. In one embodiment, the alkynyl group is substituted or unsubstituted. In one embodiment, the alkynyl group has 2 to 40 carbon atoms.

[0194] As used herein, the term "cycloalkyl group" means a fully saturated carbocyclic ring or ring system, e.g., cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl.

[0195] As used herein, the term "aromatic" refers to a ring or ring system having a conjugated pi-electron system, and includes carbocyclic aromatic (e.g., phenyl) and heterocyclic aromatic (e.g., pyridine) groups. The term includes monocyclic or fused polycyclic rings (i.e., rings which share adjacent pairs of atoms), provided that the entire ring system is aromatic.

[0196] As used herein, the term "aryl group" refers to an aromatic ring, ring system (i.e., two or more fused rings sharing two adjacent carbon atoms) whose ring structure contains only carbon, or a ring in which multiple aromatic rings are connected to each other by a single bond, -O-, -S-, -C(=O)-, -S(=O)2-, -Si(Ra)(Rb)- (Ra and Rb are each independently an alkyl group having 1 to 10 carbon atoms), an alkylene group having 1 to 10 carbon atoms substituted or unsubstituted with halogen, or C(=O)-NH-. If the aryl group is a ring system, each ring in the system is aromatic. For example, aryl groups include, but are not limited to, phenyl, biphenyl, naphthyl, phenanthrenyl, naphthacenyl, and the like. The aryl group may be substituted or unsubstituted.

[0197] As used herein, the term "heteroaryl group" refers to an aromatic ring system having one ring, multiple condensed rings, or multiple rings connected to each other by a single bond, -O-, -S-, -C(=O)-, -S(=O)2-, -Si(Ra)(Rb)- (Ra and Rb are each independently an alkyl group having 1 to 10 carbon atoms), an alkylene group having 1 to 10 carbon atoms substituted or unsubstituted with halogen, or C(=O)-NH-, in which one or more ring atoms are not carbon, i.e., are heteroatoms. In a condensed ring system, one or more heteroatoms may be present in only one ring. In a condensed ring system, one or more heteroatoms may be present in only one ring. For example, heteroatoms include, but are not necessarily limited to, oxygen, sulfur, and nitrogen. For example, the heteroaryl group can be, but is not limited to, a furanyl group, a thienyl group, an imidazolyl group, a quinazolinyl group, a quinolinyl group, an isoquinolinyl group, a quinoxalinyl group, a pyridinyl group, a pyrrolyl group, an oxazolyl group, an indolyl group, and the like.

[0198] As used herein, "halogen" refers to a stable element belonging to group 17 of the periodic table of the elements, such as fluorine, chlorine, bromine or iodine, in particular fluorine and / or chlorine.

[0199] Unless otherwise specified in this specification, the weight average molecular weight of a polymer is measured by GPC (Gel Permeation Chromatography) against a polystyrene standard sample.

[0200] The present disclosure will be described in more detail with reference to the following examples and comparative examples. However, the examples are intended to illustrate the present disclosure and are not intended to limit the scope of the present invention.

[0201] (Production of sulfide-based composite positive electrode active material) Production example 1: Li2S-LiI-CNF composite positive electrode active material Li2S and LiI were mixed in a weight ratio of 30:20. The mixture was mechanically milled using a ball mill to produce Li2S-LiI composites. The milling conditions were 25 °C, 510 rpm, and 10 h.

[0202] The Li2S-LiI composite and carbon nanofibers (CNF) were mixed in a weight ratio of 50:10. The mixture was mechanically milled using a ball mill to produce the Li2S-LiI-CNF composite. The milling conditions were 25 °C, 510 rpm, and 10 h. The Li2S-LiI-CNF composite was used as the composite positive electrode active material.

[0203] (Manufacturing all-solid-state secondary batteries) Example 1: Elastic sheet (50 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles:CNT:binder=3:1:0.28)

[0204] (Positive electrode layer manufacturing) Li2O-ZrO2 (LZO) coated LiNi as the positive electrode active material 0.8 Co 0.15 Al 0.05O2 (NCM) was prepared. The LZO-coated positive active material was prepared by the method disclosed in Korean Patent Publication No. 10-2016-0064942. Argyrodite-type crystal Li6PS5Cl (D50=0.5μm, crystalline) was prepared as a solid electrolyte. Polytetrafluoroethylene (PTFE) binder was prepared as a binder. Carbon nanofiber (CNF) was prepared as a conductive material. These materials were mixed with xylene solvent in a weight ratio of positive active material: solid electrolyte: conductive material: binder = 84:11:3:2 to form a slurry into a sheet, and then vacuum dried at 40℃ for 8 hours to prepare a positive sheet. The prepared positive sheet was placed on the carbon layer of a positive current collector made of aluminum foil coated with a carbon layer on one side, and heated roll press at 85℃ was used to prepare a positive layer. The total thickness of the positive electrode layer was about 112 μm, the thickness of the positive electrode active material layer was about 92 μm, and the thickness of the carbon-coated aluminum foil was about 20 μm.

[0205] The initial charge capacity of the positive electrode was measured using the half-cell described above. The initial charge capacity of the positive electrode active material layer was 25 mAh.

[0206] (Anode manufacturing) A 10 μm thick SUS foil was prepared as the negative electrode current collector. Silicon (Si) particles with a particle size of 1 μm were prepared as the negative electrode active material. Carbon nanotubes were prepared as the fibrous carbon-based material. The carbon nanotubes encase the carbon nanotube primary structure and the carbon nanotube secondary structure. The carbon nanotube primary structure is composed of one carbon nanotube unit. The carbon nanotube unit has a length of 200 nm to 300 nm and a diameter of about 5 to 10 nm. The carbon nanotube secondary structure is formed by agglomerating a plurality of carbon nanotube units. The carbon nanotube secondary structure has a length of about 5 μm and a diameter of about 40 nm.

[0207] 4g of mixed powder, which is a mixture of silicon (Si) particles and carbon nanotubes in a weight ratio of 3:1, was placed in a container, and 4g of NMP solution containing 7wt% Li-PAA (lithium substituted polyacrylic acid) F binder was added thereto to prepare a mixed solution. The prepared mixed solution was stirred while adding NMP little by little to prepare a slurry. The prepared slurry was applied to a SUS substrate using a bar coater, dried in air at 80°C for 10 minutes, and then vacuum dried at 40°C for 10 hours to prepare a laminate. The prepared laminate was cold roll pressed to flatten the surface, and a negative electrode having a first negative active material layer / negative current collector structure was prepared. The thickness of the first negative active material layer was about 27μm. Li-PAA was prepared by mixing polyacrylic acid and LiOH in a ratio of 1 mole of LiOH per 1 mole of polyacrylic acid COOH group, and then drying.

[0208] The initial charge capacity of the negative electrode was measured using the half-cell described above. The initial charge capacity of the first negative electrode active material layer was 9.2 mAh.

[0209] The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer was 0.37. The initial charge capacity of the positive electrode active material layer was calculated from the first open circuit voltage (1st open circuit voltage) as Li / Li + The initial charge capacity of the first negative electrode active material layer was determined by charging to 4.25 V against the second open circuit voltage. + The capacitance was determined by charging to 0.01 V relative to the battery.

[0210] In Examples 2 to 5 and Comparative Example 1, the ratios (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer, measured under the same conditions as in Example 1, were 0.24 to 0.45, respectively.

[0211] (Manufacturing of solid electrolyte layer) Argyrodite-type crystal Li6PS5Cl solid electrolyte (D 50 =3.0μm, crystalline) and 1.5 parts by weight of acrylic binder were added to 98.5 parts by weight of solid electrolyte to prepare a mixture. Octyl acetate was added to the prepared mixture while stirring to prepare a slurry. The prepared slurry was applied to a nonwoven fabric placed on a PET substrate using a bar coater and dried at 80°C in air for 10 minutes to prepare a laminate. The prepared laminate was vacuum dried at 80°C for 2 hours to prepare a solid electrolyte layer.

[0212] (Inactive material: Elastic sheet) A porous polyurethane foam sheet having a thickness of 50 μm was prepared as an elastic sheet.

[0213] (Manufacturing all-solid-state secondary batteries) A solid electrolyte layer was disposed on the negative electrode such that the first negative electrode active material layer was in contact with the solid electrolyte layer, and a positive electrode was disposed on the solid electrolyte layer such that the positive electrode active material layer was in contact with the solid electrolyte layer, to prepare a laminate.

[0214] The prepared laminate was subjected to plate pressing at 85°C and a pressure of 500 MPa for 30 minutes. This pressing process sinters the solid electrolyte layer, improving the battery characteristics. The thickness of the sintered solid electrolyte layer was about 30 μm. The density of the Li6PS5Cl solid electrolyte, an argyrodite-type crystal contained in the sintered solid electrolyte layer, was 1.6 g / cc. The area of ​​the solid electrolyte layer was the same as that of the negative electrode. An elastic sheet was further placed on the positive electrode current collector of the pressed laminate.

[0215] The laminate further including the elastic sheet was placed in a pouch and vacuum sealed to manufacture an all-solid-state secondary battery. A portion of the positive electrode current collector and a portion of the negative electrode current collector were extended to the outside of the sealed battery to be used as a positive electrode terminal and a negative electrode terminal.

[0216] Example 2: Elastic sheet (50 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles:CNT:binder=3.2:0.8:0.28) An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the composition ratio of the negative electrode active material and the fibrous carbonaceous material was changed to 3.2:0.8 (4:1).

[0217] Example 3: Elastic sheet (50 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles:CNT:binder=3.5:0.5:0.28) An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the composition ratio of the negative electrode active material and the fibrous carbonaceous material was changed to 3.5:0.5 (7:1).

[0218] Example 4: Elastic sheet (50 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles:CNT:binder=3.6:0.4:0.28) An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the composition ratio of the negative electrode active material and the fibrous carbonaceous material was changed to 3.6:0.4 (9:1).

[0219] Example 5: Elastic sheet (50 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles:CNT:binder=2:2:0.28) An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the composition ratio of the negative electrode active material and the fibrous carbonaceous material was changed to 2:2 (1:1).

[0220] Comparative Example 1: Elastic sheet (50 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles:CNT:binder=3.6:0.4:0) An all-solid-state secondary battery was manufactured in the same manner as in Example 4, except that no binder was used.

[0221] Reference Example 1: Elastic sheet (100 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (17 μm, Ag-C + binder) An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the negative electrode manufactured by the following method was used and the thickness of the elastic sheet was changed to 100 μm.

[0222] (Anode manufacturing) A 10 μm thick SUS foil was prepared as a negative electrode current collector. 4 g of a 3:1 weight ratio mixture of carbon black (CB) and silver (Ag) was placed in a container, and 4 g of an NMP solution containing 7 wt% of PVDF binder (Kureha #9300) was added thereto to prepare a mixed solution. The prepared mixed solution was stirred while adding NMP little by little to prepare a slurry. The prepared slurry was applied to a SUS substrate using a bar coater, dried in air at 80° C. for 10 minutes, and then vacuum dried at 40° C. for 10 hours to prepare a laminate. The prepared laminate was cold roll pressed to flatten the surface, and a negative electrode having a first negative electrode active material layer / negative electrode current collector structure was prepared. The thickness of the first negative electrode active material layer was about 7 μm.

[0223] Example 6: Positive electrode layer (113.8 μm, Li2S-LiI-CNF) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles:CNT:binder=3:1:0.28) An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the following positive electrode containing a sulfide-based positive electrode active material was used and the elastic sheet was omitted.

[0224] (Cathode manufacturing) The Li2S-LiI-CNF composite produced in Production Example 1 was prepared as the positive electrode active material. Argyrodite-type crystal Li6PS5Cl (D50=3.0 μm, crystalline) was prepared as the solid electrolyte. PTFE was prepared as the binder. These materials were mixed in a weight ratio of composite positive electrode active material: solid electrolyte: binder = 60: 40: 1.2 to prepare a positive electrode mixture. The positive electrode mixture was obtained by mixing using a ball mill.

[0225] The positive electrode mixture was placed on one side of a positive electrode current collector made of aluminum foil coated with carbon on one side, and plate pressed at a pressure of 200 MPa for 10 minutes to prepare a positive electrode. The total thickness of the positive electrode layer was about 113.8 μm. The thickness of the positive electrode active material layer was about 93.8 μm, and the thickness of the carbon-coated aluminum foil was about 20 μm.

[0226] In Example 1, the ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer was 0.35. The initial charge capacity of the positive electrode active material layer was 2.8 V vs. Li / Li from the first open circuit voltage. + The initial charge capacity of the first negative electrode active material layer was determined by charging the battery to a voltage of 0.01 V vs. Li / Li from the second open circuit voltage. + This was determined by charging up to

[0227] Comparative example 2: Positive electrode layer (113.8 μm, Li2S-LiI-CNF) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles:CNT:binder=3.6:0.4:0) An all-solid-state secondary battery was manufactured in the same manner as in Example 4, except that the positive electrode of Example 6 was used, no binder was used, and the elastic sheet was omitted.

[0228] Reference Example 2: Elastic sheet (50 μm) / positive electrode layer (113.8 μm, Li2S-LiI-CNF) / solid electrolyte layer (30 μm) / negative electrode layer (17 μm, Ag-C + binder) An all-solid-state secondary battery was manufactured in the same manner as in Example 6, except that the negative electrode manufactured by the following method was used and an elastic sheet having a thickness of 50 μm was used.

[0229] (Anode manufacturing) A 10 μm thick SUS foil was prepared as a negative electrode current collector. 4 g of a 3:1 weight ratio mixture of carbon black (CB) and silver (Ag) was placed in a container, and 4 g of an NMP solution containing 7 wt% of PVDF binder (Kureha #9300) was added thereto to prepare a mixed solution. The prepared mixed solution was stirred while adding NMP little by little to prepare a slurry. The prepared slurry was applied to a SUS substrate using a bar coater, dried in air at 80° C. for 10 minutes, and then vacuum dried at 40° C. for 10 hours to prepare a laminate. The prepared laminate was cold roll pressed to flatten the surface, and a negative electrode having a first negative electrode active material layer / negative electrode current collector structure was prepared. The thickness of the first negative electrode active material layer was about 7 μm. Evaluation example 1-1: Evaluation of volume change during charging and discharging (NCA positive electrode active material)

[0230] For the all-solid-state secondary batteries prepared in Example 1 and Reference Example 1, only the charging step of the first cycle was performed in the charge-discharge experiment of Evaluation Example 2 below, and then a scanning electron microscope image of the cross section of the all-solid-state secondary battery was measured to observe the thickness change.

[0231] After the first cycle charging, a lithium metal layer was formed between the first negative electrode active material layer and the negative electrode current collector.

[0232] In the all-solid-state secondary battery of Example 1, the thickness of the lithium metal layer formed between the first negative electrode active material layer and the negative electrode current collector after initial charging was approximately 8 μm, which was thinner than the thickness (34 μm) of the first negative electrode active material layer after charging.

[0233] The thickness increase after the initial charge of the all-solid-state secondary battery of Example 1 was 10% or less of the initial thickness of the all-solid-state secondary battery. As a result, the volume change during the charge and discharge process of the all-solid-state secondary battery of Example 1 was suppressed.

[0234] A 50 μm thick elastic member was used to accommodate the volume change during charging and discharging in the all-solid-state secondary battery of Example 1. As a result, the energy density of the all-solid-state secondary battery was partially reduced by including the 50 μm thick elastic member.

[0235] The thickness of the lithium metal layer formed between the first negative electrode active material layer and the negative electrode current collector after the initial charging of the all-solid-state secondary battery of Reference Example 1 was approximately 30 μm, which was thicker than the thickness (7 μm) of the first negative electrode active material layer after charging.

[0236] The thickness increase after the initial charge of the all-solid-state secondary battery of Reference Example 1 exceeded 15% of the initial thickness of the all-solid-state secondary battery. As a result, the volume change during the charge and discharge process of the all-solid-state secondary battery of Reference Example 1 was significant.

[0237] A 100 μm thick elastic member was used to accommodate the volume change during charging and discharging in the all-solid-state secondary battery of Reference Example 1. As a result, the inclusion of the 100 μm thick elastic member further reduced the energy density of the all-solid-state secondary battery.

[0238] Evaluation example 1-2: Evaluation of volume change during charging and discharging (Li2S-LiI-CNF positive electrode active material) For the all-solid-state secondary batteries prepared in Example 6 and Reference Example 2, only the charging step of the first cycle was performed in the charge-discharge experiment of Evaluation Example 2 below, and then a scanning electron microscope image of the cross section of the all-solid-state secondary battery was measured to observe the thickness change.

[0239] After the first cycle charging, a lithium metal layer was formed between the first negative electrode active material layer and the negative electrode current collector.

[0240] In the all-solid-state secondary battery of Example 6, the thickness of the lithium metal layer formed between the first negative electrode active material layer and the negative electrode current collector after initial charging was about 8 μm, which was thinner than the thickness (34 μm) of the first negative electrode active material layer after charging.

[0241] The thickness increase after the initial charge of the all-solid-state secondary battery of Example 6 was 5% or less of the initial thickness of the all-solid-state secondary battery. As a result, the volume change during the charge and discharge process of the all-solid-state secondary battery of Example 6 was negligible.

[0242] No elastic member was used to accommodate the volume change during charging and discharging in the all-solid-state secondary battery of Example 6. As a result, there was no decrease in the energy density of the all-solid-state secondary battery due to the elastic member.

[0243] The thickness of the lithium metal layer formed between the first negative electrode active material layer and the negative electrode current collector after the initial charge of the all-solid-state secondary battery prepared in Reference Example 2 was about 30 μm, which was thicker than the thickness (7 μm) of the first negative electrode active material layer.

[0244] The thickness increase after the initial charge of the all-solid-state secondary battery of Reference Example 2 exceeded 10% of the initial thickness of the all-solid-state secondary battery. As a result, the volume change during the charge and discharge process of the all-solid-state secondary battery of Reference Example 2 was significant.

[0245] A 50 μm thick elastic member was used to accommodate the increased volume change during charging and discharging in the all-solid-state secondary battery of Reference Example 2. As a result, the energy density of the all-solid-state secondary battery was partially reduced by including the 50 μm thick elastic member.

[0246] Evaluation example 2: Charge / discharge test The charge / discharge characteristics of the all-solid-state secondary batteries produced in Examples 1 to 5, Comparative Example 1, and Reference Example 1 were evaluated by the following charge / discharge test. The charge / discharge test was carried out by placing the all-solid-state secondary batteries in a thermostatic chamber at 45°C.

[0247] The first cycle is 0.5 mA / cm until the battery voltage reaches 3.9 V to 4.25 V. 2 The battery was charged for 12.5 hours at a constant current of 0.5 mA / cm until the battery voltage reached 2.5 V. 2 Discharge was carried out at a constant current of 1000 V for 12.5 hours.

[0248] Meanwhile, the charge / discharge characteristics of the all-solid-state secondary batteries prepared in Example 6, Comparative Example 2, and Reference Example 2 were evaluated by the following charge / discharge test. The charge / discharge test was performed by placing the all-solid-state secondary batteries in a thermostatic chamber at 45°C.

[0249] In the first cycle, the battery was charged at a constant current of 0.1 C for 12.5 hours until the battery voltage reached 2.5 V to 2.8 V. Subsequently, the battery was discharged at a constant current of 0.1 C for 12.5 hours until the battery voltage reached 0.3 V.

[0250] The discharge capacity of the first cycle was taken as the standard capacity.

[0251] After the second cycle, the battery was charged and discharged for up to 500 cycles under the same conditions as the first cycle. The measurement results are shown in Table 1 below. The cycle number refers to the number of cycles required for the discharge capacity to decrease to 80% of the standard capacity after the second cycle. It was considered that the more the cycle number increases, the better the life characteristics are.

[0252] [Table 1]

[0253] As shown in Table 1, the all-solid-state secondary batteries of Examples 1 to 5 exhibited excellent life characteristics by suppressing the volume change during charging and discharging and suppressing the increase in internal resistance.

[0254] The all-solid-state secondary batteries of Examples 1 to 5 had improved life characteristics compared to the all-solid-state secondary battery of Comparative Example 1 which did not contain a binder.

[0255] In the all-solid-state secondary battery of Comparative Example 1, it was determined that the life characteristics of the all-solid-state secondary battery were deteriorated due to the disconnection of the conductive path caused by the electrode detachment and / or the detachment of the negative electrode active material and the fibrous carbon-based material.

[0256] The all-solid-state secondary battery of Example 6 exhibited excellent life characteristics due to the suppression of volume change during charging and discharging and the suppression of an increase in internal resistance.

[0257] The all-solid-state secondary battery of Example 6 had improved life characteristics compared to the all-solid-state secondary battery of Comparative Example 2 which did not contain a binder.

[0258] In the all-solid-state secondary battery of Comparative Example 2, it was determined that the life characteristics of the all-solid-state secondary battery were deteriorated due to an increase in interfacial resistance between the first negative electrode active material layer and the solid electrolyte, or between the first negative electrode active material layer and the negative electrode current collector, caused by electrode detachment during charging and discharging.

[0259] Evaluation example 5: High rate characteristic evaluation The high rate characteristics of the all-solid-state secondary batteries of Examples 1 to 5, Comparative Example 1, and Reference Example 1 were evaluated by the following charge-discharge test. The charge-discharge test was carried out by placing the solid-state secondary batteries in a thermostatic chamber at 45°C.

[0260] The all-solid-state secondary batteries of Examples 1 to 5, Comparative Example 1, and Reference Example 1 were charged at a constant current of 0.1 C rate at 45° C. until the voltage reached 3.9 V (vs. Li), and then cut off at a current of 0.05 C rate while maintaining 3.9 V in constant voltage mode. Subsequently, the batteries were discharged at a constant current of 0.1 C rate until the voltage reached 2.5 V (vs. Li) during discharge.

[0261] (Formation cycle). The all-solid-state secondary battery that had undergone the chemical cycle was charged at a constant current of 0.2 C rate at 45° C. until the voltage reached 3.9 V (vs. Li). It was then discharged at a constant current of 0.2 C rate until the voltage reached 2.5 V (vs. Li) during discharge (first cycle).

[0262] The all-solid-state secondary battery that had undergone the first cycle was charged at a constant current of 0.2 C rate at 45° C. until the voltage reached 3.9 V (vs. Li). It was then discharged at a constant current of 0.33 C rate until the voltage reached 2.5 V (vs. Li) during discharge (second cycle).

[0263] The all-solid-state secondary battery that had undergone the second cycle was charged at a constant current of 0.2 C rate at 45° C. until the voltage reached 3.9 V (vs. Li). It was then discharged at a constant current of 0.5 C rate until the voltage reached 2.5 V (vs. Li) during discharge (third cycle).

[0264] The all-solid-state secondary battery that had undergone the third cycle was charged at a constant current of 0.2 C rate at 45° C. until the voltage reached 3.9 V (vs. Li). It was then discharged at a constant current of 1.0 C rate until the voltage reached 2.5 V (vs. Li) during discharge (fourth cycle).

[0265] In all charge / discharge cycles, a 10-minute rest period was allowed after each charge / discharge cycle. Some of the results of the room temperature charge / discharge experiments are shown in Table 2 below. The high rate characteristic is defined by the following Equation 1.

[0266] The high rate characteristics of the all-solid-state secondary batteries of Example 6, Comparative Example 2, and Reference Example 2 were evaluated by the following charge-discharge test. The charge-discharge test was carried out by placing the solid-state secondary batteries in a thermostatic chamber at 45°C.

[0267] The all-solid-state secondary batteries of Example 6, Comparative Example 2, and Reference Example 2 were charged at a constant current of 0.1 C rate at 45° C. until the voltage reached 2.5 V (vs. Li), and then cut off at a current of 0.05 C rate while maintaining 2.5 V in constant voltage mode. Subsequently, the batteries were discharged at a constant current of 0.1 C rate until the voltage reached 0.3 V (vs. Li) during discharge (formation cycle).

[0268] The all-solid-state secondary battery that had undergone the chemical formation cycle was charged at a constant current of 0.2 C rate at 45° C. until the voltage reached 2.5 V (vs. Li). It was then discharged at a constant current of 0.2 C rate until the voltage reached 0.3 V (vs. Li) during discharge (first cycle).

[0269] The all-solid-state secondary battery that had undergone the first cycle was charged at a constant current of 0.2 C rate at 45° C. until the voltage reached 2.5 V (vs. Li). It was then discharged at a constant current of 0.33 C rate until the voltage reached 0.3 V (vs. Li) during discharge (second cycle).

[0270] The all-solid-state secondary battery that had undergone the second cycle was charged at a constant current of 0.2 C rate at 45° C. until the voltage reached 2.5 V (vs. Li). It was then discharged at a constant current of 0.5 C rate until the voltage reached 0.3 V (vs. Li) during discharge (third cycle).

[0271] The all-solid-state secondary battery that had undergone the third cycle was charged at a constant current of 0.2 C rate at 45° C. until the voltage reached 2.5 V (vs. Li). It was then discharged at a constant current of 1.0 C rate until the voltage reached 0.3 V (vs. Li) during discharge (fourth cycle).

[0272] In all charge / discharge cycles, a 10-minute rest period was provided after each charge / discharge cycle. Some of the results of the room temperature charge / discharge experiments are shown in Table 2 below. The high rate characteristic is defined by the following Equation 1.

[0273] <Formula 1> High rate characteristic [%] = [discharge capacity at 4th cycle / discharge capacity at chemical formation cycle] x 100 [Table 2]

[0274] As shown in Table 2, the all solid state secondary batteries of Examples 1 to 5 had improved high rate characteristics compared to the all solid state secondary battery of Comparative Example 1.

[0275] In the all-solid-state secondary batteries of Examples 1 to 5, the first negative electrode active material layer contains a binder, so that the conductive path between the negative electrode active material and the fibrous carbon-based material is maintained despite the volume change of the first negative electrode active material layer during charging and discharging, and the uniformity of the electrode reaction is improved. Therefore, the high-rate characteristics of the all-solid-state secondary batteries of Examples 1 to 5 are improved compared to the all-solid-state secondary battery of Comparative Example 1.

[0276] The all-solid-state secondary battery of Example 6 had improved high-rate characteristics compared to the all-solid-state secondary battery of Comparative Example 2.

[0277] In the all-solid-state secondary battery of Example 6, the first negative electrode active material layer contains a binder, so that the conductive path between the negative electrode active material and the fibrous carbon-based material is maintained despite the volume change of the first negative electrode active material layer during charging and discharging, and the uniformity of the electrode reaction is improved. Therefore, the high-rate characteristics of the all-solid-state secondary batteries of Examples 1 to 5 are improved compared to the all-solid-state secondary battery of Comparative Example 2.

[0278] According to one embodiment, by incorporating a fibrous carbon-based material and a binder in a negative electrode active material layer having an initial charge capacity smaller than the initial charge capacity of a positive electrode active material layer, it is possible to provide an all-solid-state secondary battery in which volume change during charging and discharging is reduced and cycle characteristics are improved.

[0279] In this disclosure, "free of a or any 'ingredient'", "excluding a or any 'ingredient'", "ingredient-free", and / or the like means that the 'ingredient' is not added, selected or utilized as an ingredient in a composition or compound, but may still contain less than the appropriate amount of the 'ingredient' due to other impurities and / or external factors.

[0280] The battery management system (BMS) device according to the embodiments of the present invention described herein, and / or any other related devices or components, may be implemented utilizing any suitable hardware, firmware (e.g., application specific integrated circuit), software, or a combination of software, firmware, and hardware. For example, the various components of the device may be formed on one integrated circuit (IC) chip, or on separate IC chips. Furthermore, the various components of the device may be implemented on a flexible printed circuit film, a tape carrier package (TCP), a printed circuit board (PCB), or on one substrate. Furthermore, the various components of the device may be processes or threads that run on one or more processors in one or more computing devices, execute computer program instructions, and interact with other system components to perform the various functionality described herein. The computer program instructions are stored in a memory that may be implemented in the computing device using standard memory devices such as, for example, a random access memory (RAM). The computer program instructions may also be stored on other non-transitory computer readable media such as, for example, a CD-ROM, a flash drive, and the like. Additionally, those skilled in the art should recognize that the functionality of various computing devices may be combined or integrated into a single computing device, or the functionality of a particular computing device may be distributed across one or more other computing devices, without departing from the scope of the present disclosure.

[0281] It should be understood that the embodiments described herein should be considered only in a descriptive sense and not for the purpose of limitation. The description of a feature or aspect in each embodiment should typically be considered to be applicable to other similar features or aspects in other embodiments. Although one or more embodiments have been described with reference to the drawings, it will be understood by those skilled in the art that one or more suitable changes in form and details may be made therein without departing from the spirit and scope of the present disclosure as defined by the following claims and their equivalents. [Explanation of symbols]

[0282] 1 All-solid-state secondary battery 10 positive electrode 11 Positive electrode current collector 12 Cathode active material layer 20 negative electrode 21 Negative electrode current collector 22 First negative electrode active material layer 23 Thin Film 24 Second negative electrode active material layer 30 Solid electrolyte layer 40, 40a, 40b First inactive member 50 Second inert material

Claims

1. a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer; the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer on one surface of the positive electrode current collector, the negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer on one surface of the negative electrode current collector, the first negative electrode active material layer includes a negative electrode active material that forms an alloy or a compound with lithium, a fibrous carbon-based material, and a binder; a ratio (B / A) of an initial charge capacity (B) of the first negative electrode active material layer to an initial charge capacity (A) of the positive electrode active material layer is 0.01 to 0.75; The initial charge capacity of the positive electrode active material layer is determined by the first open circuit voltage to Li / Li + is determined by charging to the maximum charging voltage for The initial charge capacity of the first negative electrode active material layer is calculated by dividing the Li / Li by the second open circuit voltage. + An all-solid-state secondary battery as determined by charging to 0.01 V against

2. The negative electrode active material is in a particulate form, and the size of the negative electrode active material is 2 μm or less; The all-solid-state secondary battery according to claim 1 , wherein the aspect ratio of the negative electrode active material is 5 or less.

3. The negative electrode active material includes a metal-based negative electrode active material, 2. The all-solid-state secondary battery according to claim 1, wherein the metal-based negative electrode active material comprises silicon (Si), gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), or a combination thereof.

4. the first negative electrode active material layer includes a mixture of first particles of a negative electrode active material and second particles of a fibrous carbon-based material; The all-solid-state secondary battery according to claim 1 , wherein the content of the second particles is 10 to 70 wt % based on the total weight of the mixture.

5. The size of the negative electrode active material is shorter than the length of the fibrous carbon-based material, 2. The all-solid-state secondary battery according to claim 1, wherein a ratio of a size of the negative electrode active material to a length of the fibrous carbon-based material is 1:10 to 1:2000.

6. the fibrous carbon-based material is a conductive carbon-based material, The aspect ratio of the fibrous carbon-based material is 10 or more; 2. The all-solid-state secondary battery according to claim 1, wherein the fibrous carbon-based material comprises an amorphous fibrous carbon-based material, a crystalline fibrous carbon-based material, or a combination thereof.

7. The fibrous carbon-based material includes a fibrous carbon nanostructure, 2. The all-solid-state secondary battery of claim 1, wherein the fibrous carbon nanostructures include carbon nanotubes, carbon nanofibers, carbon nanobelts, or combinations thereof.

8. The carbon nanotube may include a carbon nanotube primary structure, a carbon nanotube secondary structure formed by agglomeration of a plurality of carbon nanotube primary particles, or a combination thereof; The all-solid-state secondary battery according to claim 7 , wherein the carbon nanotube primary structure is one carbon nanotube unit body.

9. The carbon nanotube primary structure includes a single-walled carbon nanotube (SWCNT), a double-walled carbon nanotube (DWCNT), a multi-walled carbon nanotube (MWCNT), or a combination thereof; 9. The all-solid-state secondary battery according to claim 8, wherein the diameter of the carbon nanotube primary structure is 1 nm to 20 nm, and the length of the carbon nanotube primary structure is 100 nm to 2 μm.

10. The carbon nanotube secondary structure includes a bundle-type carbon nanotube, a rope-type carbon nanotube, or a combination thereof; 9. The all-solid-state secondary battery according to claim 8, wherein the carbon nanotube secondary structure has a diameter of 2 nm to 50 nm and a length of 500 nm to 1000 μm.

11. the binder is a polymeric binder, the binder includes a binder including a polar functional group; the polar functional group comprises a carboxyl group, a hydroxyl group, an amide group, an aldehyde group, or a combination thereof; A part or all of the polar functional groups are substituted with lithium; The all-solid-state secondary battery according to claim 1 , wherein the binder comprises lithium-substituted polyacrylic acid.

12. The all-solid-state secondary battery of claim 1, wherein the content of the binder is 0.1 to 20 parts by weight based on 100 parts by weight of the negative electrode active material.

13. the thickness of the first negative electrode active material layer is 50% or less of the thickness of the positive electrode active material layer; The all-solid-state secondary battery according to claim 1, wherein the first negative electrode active material layer has a thickness of 1 to 50 μm.

14. a second negative electrode active material layer disposed between the negative electrode current collector and the first negative electrode active material layer, and / or between the negative electrode current collector and an electrolyte layer; the second negative electrode active material layer is a metal layer, the metal layer contains lithium or a lithium alloy, The all-solid-state secondary battery according to claim 1 , wherein a thickness of the second negative electrode active material layer is smaller than a thickness of the first negative electrode active material layer.

15. The positive electrode active material layer contains a positive electrode active material, The positive electrode active material includes a sulfide-based positive electrode active material, an oxide-based positive electrode active material, or a combination thereof; The sulfide-based positive electrode active material includes nickel sulfide, copper sulfide, Li 2 S., Li. 2 S-containing complexes or combinations thereof, 2. The all-solid-state secondary battery according to claim 1, wherein the oxide-based positive electrode active material comprises a lithium transition metal oxide, a metal oxide, or a combination thereof, the lithium transition metal oxide comprises lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminium oxide, lithium nickel cobalt mangense oxide, lithium manganate, lithium iron phosphate, or a combination thereof, and the metal oxide comprises iron oxide, vanadium oxide, or a combination thereof.

16. The positive electrode active material layer further includes at least one selected from a solid electrolyte, a conductive material, and a binder, The all-solid-state secondary battery according to claim 1 , wherein the solid electrolyte includes a sulfide-based solid electrolyte, and the conductive material includes a carbon-based conductive material.

17. the solid electrolyte layer comprises a solid electrolyte or a combination of a solid electrolyte and a gel electrolyte; The solid electrolyte includes a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a polymer solid electrolyte, or a combination thereof; The all-solid-state secondary battery according to claim 1 , wherein the gel electrolyte includes a polymer gel electrolyte.

18. The sulfide-based solid electrolyte is Li 2 S-P 2 S 5 , Li 2 S-P 2 S 5 -LiX (X is a halogen element), Li 2 S-P 2 S 5 -Li 2 O. Li 2 S-P 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 - LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S 5 - LiI, Li 2 S-B 2 S 3 , Li 2 S-P 2 S 5 -Z m S n (m and n are positive numbers, and Z is one of Ge, Zn, and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 P.O. 4 , Li 2 S-SiS 2 -Li p M.O. q (p and q are positive numbers, M is one of mP, Si, Ge, B, Al, and GaIn), Li 7-x P.S. 6-x C x (0≦x≦2, Li 7-x P.S. 6-x B x , 0≦x≦2) and Li 7-x P.S. 6-x I x (0≦x≦2), The sulfide-based solid electrolyte includes an argyrodite-type solid electrolyte, The argyrodite-type solid electrolyte is Li 6 P.S. 5 Cl, Li 6 P.S. 5 Br and Li 6 P.S. 5 I, The all-solid-state secondary battery according to claim 17, wherein the density of the argyrodite-type solid electrolyte is 1.5 to 2.0 g / cc.

19. At least one of the positive electrode current collector and the negative electrode current collector includes a base film and a metal layer disposed on one or both sides of the base film; the base film comprises a polymer, the polymer comprising polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof; 2. The all-solid-state secondary battery according to claim 1, wherein the metal layer comprises indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof.

20. The positive electrode current collector and the negative electrode current collector may further include a first inactive member disposed on one or more of the other surface of the positive electrode current collector and the other surface of the negative electrode current collector. The all-solid-state secondary battery according to claim 1 , wherein the first inactive member is an elastic member.

Citation Information

Patent Citations

  • Cathode for lithium ion secondary battery, and lithium ion secondary battery

    KR1020160064942A